Transcriptomic analysis reveals distinct mechanisms of carvone and lipopeptide crude extract from Bacillus velezensis JZ in the postharvest biocontrol of Alternaria alternata on strawberries - Lizhu Shao; Boyuan Zhang; Xueling Zhao; Yating Wang; Ziyu Wang; Miaomiao Yang; Zunzun Qi; Yuansen Hu; Na Liu; Peng Li; Li Zhang (Postharvest Biology and Technology, 2027)

A Multi-Index decision framework of optimal gasket selection for tunnel segmental joints: Integrating variable weight and extension cloud model - Huai-Na Wu; Hua-Yong Li; De-Sai Guo; Yu Li; Ren-Peng Chen (Tunnelling and Underground Space Technology, 2026)

Digital model reconstruction of shield tunnels based on 3D point cloud - Yu Li; Huai-Na Wu; Dong-Lin Feng; Si-Qi Yang; Ren-Peng Chen (Tunnelling and Underground Space Technology, 2026)

Decoding epigenetic drived heterosis in upland cotton (Gossypium hirsutum L.) through Multi-omics integration - Na Dong; Xiaoli Geng; Shoupu He; Zhen Peng; Hongge Li; Yuqing Li; Daowu Hu; Qinghua Yang; Xiaoping Pan; Xiongming Du; Qinglian Wang (Functional & Integrative Genomics, 2026)

Two-stage instance segmentation method based on Tunnel-SPVNet for shield tunnel segments - Yu Li; Huai-Na Wu; Dong-Lin Feng; Yu-Liang Li; Ren-Peng Chen (Tunnelling and Underground Space Technology, 2026)

Enhancement mechanism of tunnel linings strengthened with sprayed ultra-high-performance concrete: Full-scale experiment and simulation - Tao Chen; Huai-Na Wu; Yu Li; Si-Qi Yang; Ren-Peng Chen (Tunnelling and Underground Space Technology, 2026)

Associations of prenatal per- and polyfluoroalkyl substance exposure with neonatal birth weight z-scores: The potential mediating role of maternal glucose homeostasis - Chun-Yong Wang; Zhen-Hua Li; Hai-Yang Weng; Xiao-Yu Zhao; Shao-Lei Pu; Meng-Na Zhu; Rui He; Xia-Juan Lu; Yu-Long Kan; Kai Huang; Guo-Peng Gao; Mao-Lin Chen; et al. (Environmental Pollution, 2026)

Dynamic flavor and sensory evolution of chicken skin during thermal processing: a multi-analytical approach - Na Xu; Lisheng Li; Minyi Han; Peng Wang; Xinglian Xu (Food Research International, 2026)

Machine learning and molecular docking–driven identification of novel umami peptides from pea protein and electroencephalography (EEG) neural mechanisms analysis of their umami-enhancing effects - Peng Wang; Yue Xu; Hongbo Yi; Jun Li; Chunmin Ma; Guang Zhang; Jiawang Wang; Bing Wang; Yang Yang; Na Zhang (Food Research International, 2026)

Temporal variation in secondary metabolites and antioxidant activity during the biotransformation of American ginseng by Monascus purpureus MN 001: Molecular docking analysis of β-glucosidase-mediated ginsenoside hydrolysis - Li Zhang; Zirui Liu; Boyuan Zhang; Miaomiao Yang; Xueling Zhao; Siliang Lyu; Jiahao Bai; Siyuan Bai; Na Liu; Zhongke Sun; Peng Li; Chengwei Li; et al. (Food Bioscience, 2026)

Regulatory mechanisms of N2O emissions from latosolic red soil by different ecotypes of earthworms: Insights from microbial diversity and metagenomic analysis - Chang Wei; Chang-Wen Yun; Xiao-Qing Li; Lang-Hao Lai; Jian-Peng Gao; Meng-Ping Tang; Chun-Na Zhou; Yu-Long Zhang; Hui-Juan Xu (Environmental Pollution, 2026)

Solvation engineering of dual-polymer gel electrolyte via competitive coordination effect for durable lithium metal batteries - Xiaoya Qu; Na Li; Hao Zhai; Zhengyuan Bai; Yong Liu; Hao Wang; Shu Hong; Zhenyue Xing; Xiaodong Shi; Peng Wang (Chemical Engineering Journal, 2026)

Photodegradation process of microplastics mediated by biochar-derived dissolved organic matter: Insights from density functional theory calculations - Kunliang Jiang; Zaifeng Wang; Huacheng Xu; Zhaoliang Peng; Yuxuan Zhang; Wenkang Li; Shengkai Zhou; Qingru Wan; Na Song (Chemical Engineering Journal, 2026)

Investigation on performance-based deformation control criteria for shield tunnel linings under typical adjacent construction disturbances - Dong-Lin Feng; Yu Li; Huai-Na Wu; Si-Qi Yang; Ren-Peng Chen (Tunnelling and Underground Space Technology, 2026)

Annual energy use and economic performance of rice-based cropping systems: A three-year field study in Southwest China - Chuanhai Shu; Qingyue Cheng; Binbin Liu; Hongkun Xie; Yuanqing Shi; Mingming Hu; Hao Fu; Peng Ma; Na Li; Zhonglin Wang; Zongkui Chen; Yongjian Sun; et al. (Journal of Cleaner Production, 2026)

Exopolysaccharides from Enterococcus faecium alleviate cadmium damage in rice seedlings via regulating soil-root nitrogen metabolism - Min Zhong; Min Li; Chun-na Zhong; Zu-xuan Yan; Wei-fu Peng; Xin Cheng (Journal of Environmental Sciences, 2026)

Nature and timing of W-Sn mineralization in the Xin’anzi Deposit, Nanling Region: constraints from LA-ICP-MS cassiterite U-Pb geochronology and trace element composition - Gen-Wen He; Pei Ni; Wen-Sheng Li; Lin-Lin Peng; Gua-Hua Wang; Xin-Yue Liang; Jia-Hui Yan; Kai-Han Zhang; Li-Na Zhao (Journal of Asian Earth Sciences, 2026)

Food-derived bioactive peptides for anxiety alleviation: mechanistic insights from gut–brain axis modulation, advanced evaluation, and AI-assisted discovery - Peng Wang; Chunmin Ma; Yang Yang; Guang Zhang; Xinyu Xu; Jiawang Wang; Lulu Li; Yue Xu; Na Zhang (Food Bioscience, 2026)

Fermentation modulates wheat germ gliadin-based nanodelivery systems loaded with wheat bran polyphenols: Physicochemical properties, interaction mechanism, and functional performances - Ai-Mei Liao; Shao-Kang Yang; Meng-Yu Gao; Siyi Han; Long Pan; Jayani Chandrapala; Haiyan Gao; Dandan Zhai; Jun-Wei Chen; Na Liu; Peng Li (Food Bioscience, 2026)

TBK1 associates with TRIF and TRAF3 related IRF3, IRF7, and type I IFN signaling in large yellow croaker Larimichthys crocea - Ying Li; Wen Qi Zha; Wen Feng Cui; Meng Jia Li; Yan Mi Na Chen; Qiu Ye Huang; Qiao Yun Yang; Ying Jia Shen; Yi Lei Wang; Yong Hua Jiang; Peng Fei Zou (Fish & Shellfish Immunology, 2026)

Mango peel pectin as a high-ester emulsifier for carotenoid delivery: Structural characterization and application in low-fat ice cream - Teng-Gen Hu; Huan Zhang; Lu Li; Yu-Qing Hu; Jing Wen; Bo Zou; Jian Peng; Li-Na Cheng; Ji-Jun Wu; Geng-Sheng Xiao; Yu-Juan Xu; Yuan-Shan Yu (Carbohydrate Polymers, 2026)

Crop rotations modulate chemical transformation of dissolved organic matter during mineral surface-bound Fe(II) oxidation in paddy soils - Cong Wu; Fangling Li; Taoyuan Ouyang; Wei Peng; Yanqi Xiao; Fu Liu; Qihong Zhu; Na Zhang; Hao-Jie Cui; Wenjuan Liao (Applied Geochemistry, 2026)

Wind products from the first operational dual-frequency scatterometer WindRAD: retrieval and performance assessment - Fangli Dou; Zhixiong Wang; Xiaochun Zhai; Zhen Li; Jian Shang; Chengli Qi; Na Xu; Xiuqing Hu; Peng Zhang (Acta Oceanologica Sinica, 2026)

Molecular understanding of plant pollination, fertilization, seed development and protoplast regeneration - Jiang-Guo Meng; Pu Liu; Hanxian Xiong; Wei Wang; Gang Xu; Xu Xin; Zijun Lan; Changkai Ma; Na Wang; Xuecheng Zhang; Ce Shi; Shu Chang; et al. (Science China Life Sciences, 2026)
Sexual reproduction in plants is a tightly coordinated process that underpins biodiversity, drives speciation, and serves as a foundation for modern crop improvement. Here, we synthesize recent advances in elucidating the molecular mechanisms governing major reproductive events in flowering plants, including male and female gametogenesis, pollen-pistil communication, double fertilization, embryogenesis, and endosperm-mediated seed development. We also discuss the integration of asexual propagation through protoplast regeneration, highlighting its emerging importance in plant biotechnology. Together, these insights deepen our understanding of fundamental reproductive biology and open new opportunities for the rational design of hybrid breeding systems and stress-resilient crops, with broad implications for global food security under changing climatic conditions.

Species Divergence in Oxytocin-Dependent Yawning on a Conserved Glutamatergic Erection Circuit - Yan-Chu-Fei Zhang; Qing-Wu Zheng; Yang Lu; Hao-Yuan Wang; Jiao Cang; Xin-Rui Wu; Lin-Yao Fan; Liang Li; Ni-Na Zhang; Xiao-Yang Zhang; Jing-Ning Zhu; Jian Jing; et al. (Neuroscience Bulletin, 2026)
Yawning coupled with penile erection is a conserved neurobehavioral syndrome mediated by the paraventricular hypothalamus (PVH). However, the distinct roles of oxytocin and its co-transmitters remain unresolved. Using chemogenetics, we showed that activation of PVH oxytocin neurons was sufficient to elicit both responses, whereas silencing these neurons abolished them. Viral tracing revealed that these neurons project collaterally to the brainstem reticular nucleus and spinal cord to spatially coordinate autonomic and somatic motor outputs. By dissecting the molecular mechanisms using CRISPR-Cas9, we found that vesicular glutamate transporter 2 (VGLUT2)-dependent glutamatergic transmission provides the primary drive for both behaviors, whereas the oxytocin peptide is selectively required for yawning but dispensable for erection. Comparative analyses across rats, hamsters, and mice demonstrated that while the glutamatergic erectile circuit was conserved, mice lacked spontaneous yawning and were resistant to apomorphine-induced yawning. These findings suggest a hierarchical co-transmission framework in which fast glutamatergic signaling provides the core drive, while oxytocin confers behavioral specificity.

Retraction notice to “Algorithm developed for dynamic quantification of coal consumption for and emission from rural winter heating” [Sci. Total Environ. 737 (2020) 139762] - Yuzhe Zhang; Guorui Zhi; Sicong Guo; Wenjing Jin; Lei Wang; Jinhong Du; Miaomiao Cheng; Zhigang Xue; Yisheng Xu; Rong Shi; Yajing Lu; Hongyan Dang; et al. (Science of The Total Environment, 2026)

Intracranial EEG reveals working memory-related dynamics and connectivity in human white matter - Shen Zhang; Peng-Hu Wei; Longzhou Xu; Chao Zhang; Na Ao; Haoshu Xu; Yanfeng Yang; Lirou Tan; Zhilin Li; Yali Huang; Jin Li; Jing Liu; et al. (Science Bulletin, 2026)

Europium-labeled polystyrene tracing reveals earthworm-mediated inhibition of root uptake and reduced phytotoxicity in lettuce - Nan Chang; Shiqi Bian; Qingliang Cui; Shuling Zhao; Tianyi Qiu; Li Chen; Tao Li; Peng-yang Wang; Roland Bol; Na Wang; Zhiqin Zhang; Fengyu Huang; et al. (Journal of Hazardous Materials, 2026)

Electrochemical chlorination byproducts (ECBPs): A potential blind spot in electrochemical treatment of waste activated sludge - Dingkang Qian; Qian Zhu; Mengjiao Yuan; Ziming Xu; Jinwen Zhang; Na Li; Ming Peng; Liqiong Cao; Jianyu Gong; Jingping Hu; Huijie Hou; Jiakuan Yang; et al. (Journal of Hazardous Materials, 2026)

Foliar ammonium nitrogen at booting stage enhances 2-acetyl-1-pyrroline, modulates functional compounds, antioxidant activity, and head rice yield in fragrant rice - Guanhao Huang; Na Chen; Yingling Wu; Fukang Li; Xinyu Chen; Jiemei Peng; Zhilong Chen; Hua Tian; Zhaowen Mo (Food Research International, 2026)

Co-fermentation of Ampelopsis grossedentata with Camellia sinensis reduces bitterness, enhances sweet aroma, and generates novel bioactive theaflavin analogues - Si-Rui Li; Zi Yang; Na Song; Jia-Yi Li; Yu-Xing Zhang; Hao Li; Peng Zhang; Yu-Lan Song; Yu Sun; Kun Qian; Da-Wei Zhang; Guan-Hu Bao (Food Chemistry, 2026)

Phytoplankton responses to marine heatwaves in the Kuroshio-Oyashio Extension region: Seasonal variations and potential drivers - Hui Zhang; Na Wang; Yongqiang Chen; Peng Lian; Zhanjiu Hao; Xing Li (Marine Environmental Research, 2026)

Correction to: Cardioprotective effects of notoginsenoside R1 on myocardial remodeling and cardiac function in restraint stress‑induced MI in rats - Peng Sun; Cuiyu Han; Qian Sun; Tingting Li; Lan Li; Mingxing Shi; Pei Zhao; Lu Chen; Na Li (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Integrated NGS-MassARRAY Screening Reveals Hidden Wilson Disease Burden - Jia Tang; Hao Geng; Haihong Shi; Ting Yu; Jinping Qiao; Qingjiang Guo; Kun Wang; Jingjing Jiang; Qing Zhao; Na Nian; Yun Cheng; Shijing Wang; et al. (Phenomics, 2026)

A novel UAV-based fusion of spectral and textural features with canopy stratification for accurate estimation of vertical nitrogen distribution in cotton - Guldana Sarsen; Qiu-xiang Tang; Ya-bin Li; Long-long Bao; Yu-hang Xu; Guang-yun Sun; Jian-wen Wu; Yierxiati Abulaiti; Qing-qing Lv; Fubin Liang; Na Zhang; Ren-song Guo; et al. (Computers and Electronics in Agriculture, 2026)

Sequential oxidation and crystallization based on split-flow electrochemical oxidation with rapid filtration for sustainable phosphate recovery from phosphonate - Shiwei Xie; Zheng Wang; Na Zhang; Wenlu Li; Peng Liao (Water Research, 2026)

A differential spatiotemporal position correlation detection method for underwater moving targets - Zhanfei Peng; Haisen Li; Jian Wang; Yuhang Wei; Wankai Na; Jiani Wen (Ocean Engineering, 2026)

Time and pH regulation of the morphology and structure evolution of soybean protein fibrils: Focusing on foaming mechanism and application - Jianan Li; Zhe Wang; Bowen Yang; Xinhui Peng; Shi Liu; Na Sun; Ruihan Su; Xiaohong Tong; Huan Wang; Lianzhou Jiang (Food Hydrocolloids, 2026)

An active cling film developed from pomelo peel for synergistic preservation of Oncorhynchus mykiss: Utilizing K/Fe enzyme-like materials and natural extracts - Tao Yu; Long Cheng; Yini Zhao; Long Gu; Hangfei Gao; Zicen Liu; Li Huang; Shuyan Bai; Dongli Qin; Peng Wang; Aimin Wang; Haijiao Xie; et al. (Food Packaging and Shelf Life, 2026)

Dual covalent–hydrogen-bond networks enable synergistic thermo-mechanical performance and durability in polyimide films - Luling He; Xiong Li; Jiamei Liu; Yu Zhang; Na Song; Tongle Xu; Peng Ding (Chemical Engineering Journal, 2026)

Andrographolide induces testicular damage by triggering ferroptosis in Sertoli cells via disruption of β-TrCP-mediated ATF4 ubiquitination and degradation - Jiaqi Li; Zhengxin Lu; Nan Zhang; Xiaowei Zhou; Yuanbiao Ma; Jia-qi Li; Yimu Zhang; Zhewen Deng; Na Lin; Peng Yue; Yilin Yang; Qi Zhang; et al. (Chemico-Biological Interactions, 2026)

Characterization of a new diterpenoid glycoside and chemotaxonomical significance of secondary metabolites from Excoecaria acerifolia - Na-Li Song; Jia-Peng Wang; Li-Ping Yang; Sheng-Qi Zhang; Xia Zhao; Le Cai; Zhong-Tao Ding (Biochemical Systematics and Ecology, 2026)

Influence of salinity on the dynamic improving nutritional value of channel catfish (Ictalurus punctatus): Insights from targeted and untargeted metabolomics and antioxidant capacity analysis - Zhen Li; Yali Yu; Quanyou Guo; Na Lin; Xiaorong Lu; Jie Peng; Tao Mao; Yuntao Zhou; Lang Zhang; Liu Fang (Aquaculture, 2026)

Organic fertilization alleviates soil sickness in monoculture systems by driving pathogen-suppressive rhizosphere community assembly - Tong Peng; Chuanji Zhang; Xiaoqi He; Zhenyu Cheng; Junjie Li; Yanfang Song; Ziyu Liu; Meiyun Pu; Yi Yan; Panshuai Fei; Yurong Bi; Xiaofan Na (Plant and Soil, 2026)

Activating FcγRI inhibits RIG-I-mediated host antiviral innate immunity by FGR during PRRSV-ADE infection - Peng-li Xu; Yi-han Li; Fa-hao Li; Shi-jie Zhao; Wen Li; Jing Chen; Ping-an Xia; Yi-na Zhang (Veterinary Microbiology, 2026)

Superhydrophilic and underwater superoleophobic chitin nanocrystals/ palygorskite nanoclays membrane for multifunctional oil/water emulsion separation - Chenglong Wang; Chenglan Zhang; Jiajie Li; Chun Song; Chenchen Lu; Chenxin Guo; Chunyu Chang; Bo Duan; Na Peng (Journal of Environmental Chemical Engineering, 2026)

Improvement of the quality of whole grain highland barley slurry through thermal pre-treatment under turbulent conditions: Lubrication, microstructure, and rheological - Bo-Hui Li; Yi-Peng Bai; Xiao-Na Guo; Xiao-Hong Sun; Ke-Xue Zhu (Food Chemistry, 2026)

Validation and Correction of In-Orbit Tangent Height for the Ozone Monitoring Suite-Limb onboard FY-3F - Song Liu; Yuan Li; Na Xu; Lin Chen; Peng Zhang; Minzheng Duan; Yapeng Wang; Jiachen Wang; Ruonan Jiang (Journal of Meteorological Research, 2026)

Methanobrevibacter smithii induces postnatal growth retardation through blunting hepatic ketone body metabolism - Ming Qi; Tongxing Song; Yuankun Deng; Na Li; Nan Wang; Andong Zha; Qing Ye; Chengming Wang; Yirui Shao; Yucheng Zhu; Ming Sun; Jens Walter; et al. (Science Bulletin, 2026)

Multifunctional pomelo peel cellulose/lysine/ZIF-8 porous foam with honeycomb structure: Adsorption performance and mechanism - Haize Su; Weipeng Qiu; Tenggen Hu; Shaohua Luo; Jinling Wu; Xiaowen Zhong; Na Li; Hao Su; Zhizhou Ling; Zhenlin Xu; Hong Wang; Peng Wen (Carbohydrate Polymers, 2026)

Cardioprotective effects of notoginsenoside R1 on myocardial remodeling and cardiac function in restraint stress-induced MI in rats - Peng Sun; Cuiyu Han; Qian Sun; Tingting Li; Lan Li; Mingxing Shi; Pei Zhao; Lu Chen; Na Li (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

The pivotal role of mitochondria in the pathogenesis and treatment of liver failure: a comprehensive review - Qing Peng; Liyuan Hao; Shenghao Li; Fei Yu; Na Li; Xinyu Luo; Jiayun Yue; Qianlan Luo; Kangning Zheng; Xiaoyu Hu (Molecular and Cellular Biochemistry, 2026)

Pathogenicity of Porcine reproductive and respiratory syndrome virus in the reproductive system of female piglets: Pathological damage to the uterine horns and developmental arrest - Yi-Xin Yan; Ying Guan; Lei Zhao; Han-Yu Li; Tong Xu; Li-Na Shao; Si-Yuan Lai; Yi Qing; Liang-Peng Ge; Zuo-Hua Liu; Jing Sun; Xiu Zeng; et al. (Veterinary Microbiology, 2026)

Long-term waterproof performance of EPDM sealing gaskets considering aging-induced stress relaxation - Hua-Yong Li; Huai-Na Wu; Hong Cao; Ren-Peng Chen (Tunnelling and Underground Space Technology, 2026)

Microwave-induced low-temperature treatment for efficiently removing PCDD/Fs from secondary copper smelting fly ash: key parameters, additive agents, and internal mechanism - Siyu Gong; Yifan Niu; Yongchao Yang; Jinhao Zheng; Na Li; Shaohua Ju; Hongbo Peng (Fuel, 2026)

Research on pore structure and fractal characteristics of low-medium rank coals before and after acidification with H2S aqueous solution based on NMRC - Yan Wang; Haichao Wang; Xin Li; Chao Jia; Xiaoqian Cheng; Na Zhang; Bo Wang; Peng Lai; Zhenpeng Hu; Zhengkai Liao (Fuel, 2026)

Self-driven degradation and protection against chemical warfare agent simulants via MOF-808 derived bipolar membrane interfaces - Na Gao; Xiao-Peng Li; Xinbo Wang; Li Li; Heguo Li; Fen Luo; Yue Zhao; Huan Xu; Liang Wu (Chemical Engineering Journal, 2026)

Enhanced carbohydrate metabolism in subdominant microbes drives rice straw decomposition under nitrogen addition: A four-month study in winter - Na Zhang; Longtao Li; Chunhua Dong; Zhongxiu Rao; Hua Peng; Fengqiu Huang (Applied Soil Ecology, 2026)

Contrasting temperature responses of photosynthesis and respiration amplify reduction in carbon sink under water stress conditions in a temperate semi-arid steppe - Xinhao Li; Tianshan Zha; Peng Liu; Xin Jia; Yun Tian; Hongxian Zhao; Jinshi Jian; Na Deng (Agricultural and Forest Meteorology, 2026)

Enhancing Blood Fingerprints with Multicolored Conjugated Polymers: A Fluorescent Strategy with Python-Based Quantitative Assessment - Zimin Zhang; Yuhao Zhang; Xuelian Jiang; Na Rao; Mingzhu Wu; Ying Li; Di Peng (Journal of Fluorescence, 2026)

Prediction on the waterproof performance of EPDM gaskets in shield tunnels considering the stress state of compression and tension - Ren Wu; Huai-Na Wu; Hua-Yong Li; Xin-Xin Yang; Dong-Lin Feng; Hong Cao; Ren-Peng Chen (Tunnelling and Underground Space Technology, 2026)

Application of an innovative BMask R-CNN-DAT enhanced with feature extraction and boundary awareness in tunnel leakage detection - Yu Li; Huai-Na Wu; Hong-Zhan Cheng; De-Sai Guo; Ren-Peng Chen (Tunnelling and Underground Space Technology, 2026)

Genome analysis and secondary metabolite characterization of Bacillus velezensis JZ as a potential biocontrol agent - Li Zhang; Lizhu Shao; Boyuan Zhang; Yuting Li; Ziyu Wang; Shuhong Song; Miaomiao Yang; Boshen Wang; Dandan Zhai; Na Liu; Peng Li (Physiological and Molecular Plant Pathology, 2026)

Liquid-derived carbon encapsulated nanoporous SiOx anode for long-cycle lithium-ion batteries - Liewu Li; Chufang Chen; Qianqian Jiang; Zhencheng Huang; Jie Peng; Haoran Wei; Xiaoyu Gong; Na Feng; Shenghua Ye; Xuming Yang; Xiangzhong Ren; Jianhong Liu; et al. (Chemical Engineering Journal, 2026)

Comprehensive assessment of secondary metabolite diversity and in vitro anti-diabetic properties in Sanghuangporus quercicola cultured under different conditions - Mingxing Yu; Na Zhang; Xiaofeng Ma; Xiaoshuang Zhou; Shude Yang; Weihang Peng; Yin Li; Yuejun Mu; Xianhao Cheng; Rui Zhang; Yongfei Ming (Systems Microbiology and Biomanufacturing, 2026)

A three-dimensional coupling evaluation model for carbon source-sink in riparian zones - Na Li; Juan Peng; Feng Yan (Journal of Hydrology, 2025)

Separation and detection of ginsenosides: Challenges, industrial implications, and developments - Anqi Liu; Junjun Zhou; Yiling Luo; Yingbo Li; Yu Yang; Zibo Meng; Lixia Zhou; Hanlei Zhang; Na Liu; Ming Hui; Dandan Zhai; Peng Li (Food Research International, 2025)

SOX11-mediated CBLN2 Upregulation Contributes to Neuropathic Pain through NF-κB-Driven Neuroinflammation in Dorsal Root Ganglia of Mice - Ling-Jie Ma; Tian Wang; Ting Xie; Lin-Peng Zhu; Zuo-Hao Yao; Meng-Na Li; Bao-Tong Yuan; Xiao-Bo Wu; Yong-Jing Gao; Yi-Bin Qin (Neuroscience Bulletin, 2025)
Neuropathic pain, a debilitating condition caused by dysfunction of the somatosensory nervous system, remains difficult to treat due to limited understanding of its molecular mechanisms. Bioinformatics analysis identified cerebellin 2 (CBLN2) as highly enriched in human and murine proprioceptive and nociceptive neurons. We found that CBLN2 expression is persistently upregulated in dorsal root ganglia (DRG) following spinal nerve ligation (SNL) in mice. In addition, transcription factor SOX11 binds to 12 cis -regulatory elements within the Cbln2 promoter to enhance its transcription. SNL also induced SOX11 upregulation, with SOX11 and CBLN2 co-localized in nociceptive neurons. The siRNA-mediated knockdown of Sox11 or Cbln2 attenuated SNL-induced mechanical allodynia and thermal hyperalgesia. High-throughput sequencing of DRG following intrathecal injection of CBLN2 revealed widespread gene expression changes, including upregulation of numerous NF-κB downstream targets. Consistently, CBLN2 activated NF-κB signaling, and inhibition with pyrrolidine dithiocarbamate reduced CBLN2-induced pain hypersensitivity, proinflammatory cytokines and chemokines production, and neuronal hyperexcitability. Together, these findings identified the SOX11/CBLN2/NF-κB axis as a critical mediator of neuropathic pain and a promising target for therapeutic intervention.

Jaagichlorella menglunensis sp. nov. (Watanabeales, Chlorophyta), a new coccoid green alga isolated from China - Huiyin Song; Rongli Guan; Tian He; Langyue Zhang; Tiantian Li; Junfei Zhou; Yuxin Hu; Shuyin Li; Feng Liu; Lun Li; Na Zhang; Huafeng Xiao; et al. (Journal of Oceanology and Limnology, 2025)

Erratum to ‘mechanisms of exopolysaccharide synthesis by Streptococcus thermophilus IMAU20246 determined by the carbon source’[Food Chemistry 481 (2025) 144069] - Qingting Peng; Haimin Hu; Annaer Dai; Na Wu; Hong Li; Tong Dan (Food Chemistry, 2025)

Engineered albumin host for ratiometric fluorescent indicator-displacement assay: Distinguishing testosterone from estrone and estradiol - Yuting Luo; Linhui Peng; Zhang Lin; Zhiqing Xun; Na Li; Naiyu Liu; Yalong Wang; Xinfeng Du; Tianyi Qin; Bin Liu; Mingqiang Zhu (Chemical Engineering Journal, 2025)

Efficacy and safety of an mRNA encoding neutralizing antibody against SARS-CoV-2 in non-human primates - Hang Chi; Suo-Qun Zhao; Yun-Peng Liu; Xiao-Chuan Xiong; Xia Zhong; Xing-Xing Suo; Xing-Yao Huang; Can Yue; Jing-Jing Zhang; Zhe Cong; Na Li; Fei-Xue Du; et al. (Science Bulletin, 2025)

Unveiling the multifunctional roles of karrikin as a novel phytohormone in cadmium detoxification of bread wheat (Triticum aestivum L.) - Ting Zhou; Yu-shan Xiao; Yong-le Fu; Hao Li; Rui Cui; Ying-na Feng; Zheng-fu Zhou; Ying-peng Hua (Journal of Hazardous Materials, 2025)

Identifying omitted high reactive VOCs emission sources in China based on new speciated emission inventory - Di Wang; Jinhong Du; Li Yang; Jinmin Zhao; Xinmin Zhang; Zhihao Zhang; Wenjuan Zhao; Weiqi Zhang; Yuzhe Zhang; Jinghua Ma; Wenjing Jin; Yanjun Ren; et al. (Journal of Cleaner Production, 2025)

Mitochondrial energy reprogramming via dECM/GP@EVs@Gpnmb to prevent post-myocardial infarction heart failure - Na Li; Ying Wang; Ling Yuan; Shuang Peng; Zhansheng Hu; Baoquan Wang; Dan Zhang; Longxiang Su; Huiping Wu (Chemical Engineering Journal, 2025)

Deep soil moisture has limited impact on mitigating drought stress effects on plant transpiration in a subtropical secondary forest - Ji Zhang; Na Liu; Cicheng Zhang; Xinping Zhang; Xinguang He; Wulin Jiang; Jiajie Li; Ziwei Zhan; Dejing Peng; Dongjie Lv; Suixia Ni (Plant and Soil, 2025)

MSTC: a unified encoding method for geophysical big data retrieval - Henggao Geng; Suping Peng; Tao He; Na Xu; Zhangang Wang; Xianlei Xu; Xiaoqin Cui; Wenfeng Du; Yang Li; Kunheng Li (Earth Science Informatics, 2025)

Polylactic acid microplastics and earthworms drive cadmium bioaccumulation and toxicity in the soil–radish health community - Changcheng Chen; Na Zheng; Huicheng Zhu; Qirui An; Xiaoqian Li; Liyuan Peng; Zhifei Xiu (Journal of Hazardous Materials, 2025)

Performance and mechanism of tetracycline degradation by CuCo2O4 nanomaterial activated periodate - Peng Xu; Na Li; Jingwei Ma; Jiafan Yao; Baolin Hou (Environmental Pollution, 2025)

A novel multi-functional PVA- alginate hydrogel with dynamic bond crosslinking for infected wound repair - Huanghe Zeng; Lingling Tang; Li Huang; Na Yang; Xingyue Chen; Xi Peng; Zhengxian Chen; Jianxiu Guo; Jie Weng; Tailin Guo (Carbohydrate Polymers, 2025)

CD73 polymorphisms are associated with schizophrenia - He-Xia Peng; Li-Li Zhang; Dan Jiang; Na Jian; Ting-Mei Zhang; Jia-Guo Luo; Hai-Yan Yin (Purinergic Signalling, 2025)
Ecto-5’-nucleotidase/CD73 enzyme plays a key role in the regulation of extracellular adenosine levels, thereby exerting influence on adenosine homeostasis. Emerging evidence suggests that perturbations in purines and ecto-5’-nucleotidase activity are associated with an augmented susceptibility to schizophrenia. However, the precise impact of genetic variations in CD73 on individuals with schizophrenia remains poorly understood. Here, our study demonstrated that rs3734442 allele and rs4431401 heterozygote were conferred a significant risk of schizophrenia disease (rs3734442: odds ratio, 0.556; 95% CI, 0.375 to 0.825; p = 0.004; rs4431401: odds ratio, 1.881, 95% CI, 1.117 to 3.166; p = 0.020). Comparing different genders, we observed a significant association between rs3734442 genotypes and male cases (rs3734442: odds ratio, 0.452; 95% CI, 0.257 to 0.796; p = 0.007). Likewise, there was a significant association between rs4431401 genotypes and male patients (rs4431401: odds ratio, 2.570; 95% CI, 1.196 to 5.522; p = 0.015). Based on family history and antipsychotics medication usage, our data reveals that the rs9444348 allele exhibits the most significant association with familial susceptibility to schizophrenia (odds ratio, 1.541; 95% CI, 1.009 to 2.353; p = 0.048 for A vs G). Moreover, individuals carrying variants of rs6922, rs2229523, and rs2065114 while being treated with clozapine demonstrate a higher frequency proportion compared to those receiving risperidone treatment ( p = 0.035; p = 0.049; p = 0.027 respectively). Additionally, our results indicate that patients with GG genotype of rs9444348 had significantly higher likelihood of using clozapine instead of sulpiride ( p = 0.048). Overall, our data strongly suggest that genetic variations in CD73 are significantly associated with schizophrenia risk and may serve as valuable resources for identifying therapeutic targets.

Tissue and cell types infected by Ecytonucleospora hepatopenaei (EHP) - Yuan Wang; Shi-ting Lin; Ming Zhao; Peng Di; Jun-fang Zhou; Shou-hu Li; Yan-qing Huang; Ying Na; Xin-cang Li; Wen-hong Fang (Journal of Invertebrate Pathology, 2025)

Mechanisms of exopolysaccharide synthesis by Streptococcus thermophilus IMAU20246 determined by the carbon source - Qingting Peng; Haimin Hu; Annaer Dai; Na Wu; Hong Li; Tong Dan (Food Chemistry, 2025)

Flavor enhancement of soy protein isolate hydrolysates through the Maillard reaction and identification of saltiness-enhancing peptides - Hongbo Yi; Jun Li; Peng Wang; Shengnan Wang; Xiaofei Guo; Danshi Zhu; He Liu; Na Zhang (Food Bioscience, 2025)

Periodate activation for tetracycline degradation with MoS2/MnFe2O4 nanocomposite: Efficiency and Mechanistic insights - Peng Xu; Na Li; Jiafan Yao; Jingwei Ma; Baolin Hou (Environmental Pollution, 2025)

SSA-TCN: satellite clock offset prediction during outages of RTS stream - Lin Zhao; Zhibo Na; Liang Li; Peng Cui (GPS Solutions, 2025)

UV-B stress reshapes root-associated microbial communities and networks, driven by host plant resistance - Chuanji Zhang; Na Gao; Xiaofan Na; Kaile Li; Meiyun Pu; Hao Sun; Yanfang Song; Tong Peng; Panshuai Fei; Junjie Li; Zhenyu Cheng; Xiaoqi He; et al. (Soil Biology and Biochemistry, 2025)

The effect of 254 nm ultraviolet C promoting ethanol-induced gastric injury healing - A potential physical factor therapy - Xiao Zhang; Dong-mei Li; Hong-long Chen; Xi-sheng Lin; Su-su Li; Le Yu; Nan Peng; Li-kang Wang; Na Wang; Yue-ming Gao (Journal of Photochemistry and Photobiology B: Biology, 2025)

Rapid absolute quantification of glucose and fructose isomers in honey using a boronic acid-based reactive matrix by MALDI-TOF/TOF tandem mass spectrometry - Zhang-Na Qin; Jia-Min Chen; Jia-Wei Li; Zhen-Peng Zhen; Qi-Zhao Chen; Zhi-Qiang Zhang; Gui-Hua Wang; Yu-Feng Gao (Food Chemistry, 2025)

Impact of fermentation duration in fermented glutinous rice wine dough procedure on the staling of Chinese steamed bread - Jia-Xuan Shang; Jia-Xuan Li; Feng-Ping Qin; Yi-Peng Bai; Xiao-Na Guo; Ke-Xue Zhu; Jun-Jie Xing (Food Bioscience, 2025)

Mechanism of flavor changes in Northern Pike (Esox lucius) during refrigeration revealed by UHPLC-MS metabolomics and GC-IMS - Shijie Bi; Gao Gong; Na Li; Peng Gao; Tianyu Hou; Jinfang Zhu; Batuer Abulikemu (Food Bioscience, 2025)

Multi-dimensional deconstruction and theme evolution of China's energy policy - Xiuzhu Zang; Tao Lv; Xiaoran Hou; Xu Deng; Xiao Peng; Na Li (Energy Policy, 2025)

Graph Neural Networks and Multimodal DTI Features for Schizophrenia Classification: Insights from Brain Network Analysis and Gene Expression - Jingjing Gao; Heping Tang; Zhengning Wang; Yanling Li; Na Luo; Ming Song; Sangma Xie; Weiyang Shi; Hao Yan; Lin Lu; Jun Yan; Peng Li; et al. (Neuroscience Bulletin, 2025)

Clinical characteristics and associated factors of macrolide-resistant mycoplasma pneumoniae pneumonia in children: a systematic review and meta-analysis - Shuo Yang; Xinying Liu; Yaowei Han; Huizhe Wang; Yunzheng Mei; Haokai Wang; Na Zhang; Yingying Peng; Xinmin Li (European Journal of Clinical Microbiology & Infectious Diseases, 2025)

Development of a highly efficient seeding breeding system of Notopterygium incisum - Si Cheng Yao; Qiao Jia Peng; Na Su; Yuan Yuan Jiang; Jin Qiu Liao; Long Wang; Xue Xue Deng; Rui Wu Yang; Xiang Yun Chen; Li Zhang (Plant Biotechnology Reports, 2025)

Hydrogen peroxide regulated split-type electrochemiluminescence sensing platform for non-invasive detection of gastric cancer-associated D-amino acids - Juan Li; Ming-Chun Lai; Ya-Meng Zhong; Ya-Ling Chen; Na Wu; Wei Chen; Hua-Ping Peng (Analytica Chimica Acta, 2025)

Regulation strategies of microplastics with different particle sizes on cadmium migration processes and toxicity in soil-pakchoi system - Qirui An; Na Zheng; Changcheng Chen; Xiaoqian Li; Yining Ji; Liyuan Peng; Zhifei Xiu; Qiuyan Lin (Journal of Hazardous Materials, 2025)

Associations of multiple metals exposure with immunoglobulin levels in pregnant women: Hangzhou Birth Cohort Study - Jiena Zhou; Lanfei Jin; Yexinyi Zhou; Kunhong Zhong; Kegui Huang; Qi Zhang; Jun Tang; Xue Zhang; Lihe Peng; Shuai Li; Na Lv; Dongdong Yu; et al. (Journal of Environmental Sciences, 2025)

Spatial and temporal distribution, fate, and potential health risks of microplastics in urban indoor air - Liyuan Peng; Na Zheng; Qirui An; Xiaoqian Li; Siyu Sun; Yunyang Li; Jingze Yu; Fan Shao; Yingxi Qiu; Shuyue Zhang (Gondwana Research, 2025)

Polyhalogenated carbazoles contamination in East China Sea sediments: Spatial distribution, source apportionment, and ecological risk assessment - Li-Xin Kou; Xiao-Yu Zhang; Zi-Cen Zuo; Na Liu; Zhen He; Gui-Peng Yang (Environmental Research, 2025)

Root exudates drive root avoidance of maize in response to neighboring wheat - Xiao-Tong Yin; Fang-Fang Zhang; Rui-Peng Yu; Na Liu; Wei-Ping Zhang; Dario Fornara; Liesje Mommer; Xue-Xian Li; Long Li (Plant and Soil, 2025)

Inhibition of Vascular Endothelial Growth Factor Reduces Photoreceptor Death in Retinal Neovascular Disease via Neurotrophic Modulation in Müller Glia - Shuang Gao; Sha Gao; Yanuo Wang; Lu Xiang; Hanwei Peng; Gong Chen; Jianmin Xu; Qiong Zhang; Caihong Zhu; Yingming Zhou; Na Li; Xi Shen (Molecular Neurobiology, 2025)

Oxidative Stress-mediated Loss of Hippocampal Parvalbumin Interneurons Contributes to Memory Precision Decline After Acute Sleep Deprivation - Yu-zhu Gao; Kai Liu; Xin-miao Wu; Cui-na Shi; Qiu-li He; Hai-peng Wu; Jian-jun Yang; Hao Yao; Mu-huo Ji (Molecular Neurobiology, 2025)

A dual-functional paper-based analytical device for ultrasensitive detection of peanut allergen-specific IgE - Ze-Nan Ma; Jun-Jie Ding; Xin-Qiao Shi; Ying Yuan; Meng-Tian Wang; Li-Na Yu; Xiao-Jun Wang; Peng Shen (Analytica Chimica Acta, 2025)

Hydroxylamine enhanced zero-valent copper/persulfate oxidation systems: Rapid corrosion of Cu(0) and reduction of Cu(Ⅱ) - Peng Xu; Jiaqi Feng; Na Li; Jiafan Yao; Guangchao Li; Baolin Hou (Journal of Environmental Chemical Engineering, 2025)

Characterization and Assessment of Sheep-Origin Probiotic Bacillus licheniformis B63 Strain for Potential Use in Intestinal Health and Disease - Meng Hou; Yabin Lu; Mengjun Ye; Na Li; Yawei Sun; Gang Yao; Jinquan Wang; Fangfang Yin; Qimin Peng; Sheng Jia; Rui Shi; Xuxiang Wang (Probiotics and Antimicrobial Proteins, 2025)

An extensin-like gene OsPEX1 plays key roles in temperature stress response in rice - Jieni Li; Ao Li; Yue Wang; Zhi-Hao Wu; Xiaohong Li; Jie Meng; Chen Liang; Yuxin Song; Na Liu; Wanzhen Gao; Haifeng Peng; Yingxue Yang; et al. (Plant Cell, Tissue and Organ Culture (PCTOC), 2025)

Waterproofing enhancement mechanism of the double sealing gaskets: Experimental test and theoretical analysis - Hua-Yong Li; Huai-Na Wu; Dong-Lin Feng; Lei Liu; Qing-long Cui; Ren-Peng Chen (Tunnelling and Underground Space Technology, 2025)

Angular normalization of GOES-16 and GOES-17 land surface temperature over overlapping region using an extended time-evolving kernel-driven model - Boxiong Qin; Shuisen Chen; Biao Cao; Yunyue Yu; Peng Yu; Qiang Na; Enqing Hou; Dan Li; Kai Jia; Yingpin Yang; Tian Hu; Zunjian Bian; et al. (Remote Sensing of Environment, 2025)

Sesquiterpenoids from Inula britannica and their potential mechanism for immunomodulation - Hui-Lin Zhang; Na Wang; Xu-Liu Shi; Miao-Miao Wang; Qi-Meng Zhu; Jing Chang; Yan-Li Feng; Juan Zhang; Feng Qiu; Cheng-Peng Sun (Phytochemistry, 2025)

The effect of chloride ion on the reinforcement of zero-valent copper activated peroxysulphate - Peng Xu; Na Li; Pengfei Zhu; Ruoxi Wu (Journal of Water Process Engineering, 2025)

Auxin regulates leaf senescence and nitrogen assimilation to promote grain filling in maize (Zea mays L.) - Na Jiang; Peng Wang; Zhiqi Yang; Changwei Li; Yixiang Xia; Xiangmin Rong; Yongliang Han; Lan Yang (Field Crops Research, 2025)

Correction to: Scorpion Venom Heat-Resistant Peptide is Neuroprotective Against Cerebral Ischemia-Reperfusion Injury in Association with the NMDA-MAPK Pathway - Xu-Gang Wang; Dan-Dan Zhu; Na Li; Yue-Lin Huang; Ying-Zi Wang; Ting Zhang; Chen-Mei Wang; Bin Wang; Yan Peng; Bi-Ying Ge; Shao Li; Jie Zhao (Neuroscience Bulletin, 2025)

AMPK activation by dietary acadesine improves fillet texture in large yellow croaker (Larimichthys crocea) fed a linseed oil-based diet - Shengdi Chen; Zihan Sun; Ningning Liu; Chenbin Yang; Na Li; Lu Li; Chaoqing Wei; Binlun Yan; Huan Gao; Peng Tan; Hua Mu (Aquaculture, 2025)

Experimental and numerical study on the waterproof performances of the sealing gaskets under coupled compression-shear stress - Huai-Na Wu; Hua-Yong Li; Lei Liu; Xin-Xin Yang; Ren-Peng Chen (Tunnelling and Underground Space Technology, 2025)

Benzofurans and dibenzofurans from galls on twigs of the endangered Chinese endemic tree Parrotia subaequalis and their inhibitory properties against Staphylococcus aureus and ATP-citrate lyase - Peng-Jun Zhou; Xi-Ying Wu; Ze-Yu Zhao; Yi Zang; Zhong-Shuai Sun; Yue-Ling Li; Na Li; Juan Xiong; Yeun-Mun Choo; Ze-Xin Jin; Jia Li; Jin-Feng Hu (Phytochemistry, 2025)

Investigation of an outbreak of hepatitis E virus 4d reveals the importance of good kitchen hygiene - Yuan Sun; Yulou Sun; Sisi Tan; Na Li; Kui Wang; Xinxin Zhang; Bingyang Li; Feng Hao; Cuiqun Sun; Peng Chen (International Journal of Food Microbiology, 2025)

Catalytic degradation of tetracycline by nano-sized Cu3V2O8 ∙H2O activated periodate: Performance and mechanism - Peng Xu; Jiafan Yao; Na Li; Jiaqi Feng; Ruoxi Wu; Baolin Hou (Journal of Water Process Engineering, 2024)

Intimate microbe-water-mineral interactions mediate alkalization in the pyroxene-rich iron ore mines in Panxi area, Southwest China - Yu He; Yongzhe Li; Yue Pan; Jianying Shang; Weimin Sun; Meng Wang; Hao Fan; Robert A. Sanford; Na Wei; Shuming Peng; Daihong Xie; Weiguang Zhang; et al. (Journal of Hazardous Materials, 2024)

Tissue-specific distribution and fatty acid content of PFAS in the northern Bohai Sea fish: Risk-benefit assessment of legacy PFAS and emerging alternatives - Zhifei Xiu; Na Zheng; Qirui An; Changcheng Chen; Qiuyan Lin; Xiaoqian Li; Sujing Wang; Liyuan Peng; Yunyang Li; Huicheng Zhu; Siyu Sun; Shuai Wang (Journal of Hazardous Materials, 2024)

A smartphone-based supramolecular biosensor for portable and rapid detection of buprofezin in real food samples - Yilin Zhan; Na Li; Tianyi Qin; Linhui Peng; Weihua Deng; Zhongyong Xu; Lei Wang; Immanuel David Charles; Bin Liu (Food Chemistry, 2024)

Assessment of the impact of whey protein hydrolysate on myofibrillar proteins in surimi during repeated freeze–thaw cycles: Quality enhancement and antifreeze potential - Xinyan Peng; Yunying Li; Juan Yu; Yonglin Gao; Xinxin Zhao; Na Jia (Food Chemistry, 2024)

Identification of novel salt-enhancing peptides in soy protein and molecular docking studies with transmembrane channel-like 4 (TMC4) - Jun Li; Peng Wang; Hongbo Yi; Shengnan Wang; He Liu; Na Zhang (Food Bioscience, 2024)

Exogenous melatonin improves peanut field productivity and quality at reduced nitrogen application - Lijie Li; Xiangguo Cheng; Yi Zhang; Dana Kohtz; Xiaohui Wang; Xiaotian Zhang; Xiangjun Kong; Huiyun Xue; Peipei Jia; Na Bai; Zengqiang Li; Peng Xiao; et al. (Field Crops Research, 2024)

Effectiveness and impact factors of passive convergence-permeable reactive barrier (PC-PRB): Insights from tracer simulation study - Kaixuan Zheng; Yihao Li; Shiyang Tao; Jie Ding; Fuli Li; Xiangqin Peng; Jieyong Ou; Yanzhi Chen; Lei Lei; Wei Wang; Hongtao Wang; Na Liu; et al. (Journal of Environmental Management, 2024)

Understanding of manganese-sulfur functionalized biochar: Bridging effect enhanced specific passivation of lead in soil - Gaoyuan Gu; Shuyi Yang; Na Li; Chong Peng; Yun Li; Tao E (Environmental Pollution, 2024)

RNA reading protein YTHDF2 mediates Benzo(k)fluoranthene induced male reproductive injury by regulating the stability of BCL2 - Ya-wen Li; Dan-dan Wang; Hong-qiang Chen; Yong Zeng; Na Wang; Yu Shi; Jiang-ying Li; Ni-ya Zhou; Da-peng Wang; Qing Chen; Xue Han; Jia Cao; et al. (Environmental Pollution, 2024)

Co-production of plant- and microbial- proteins from waste tobacco leaves by optimizing alkaline extraction and strengthening pectin bioconversion - Yingjie Guo; Guodong Liu; Sulei Li; Na Chen; Zhongfeng Zhang; Peng Zhang; Liwei Gao (Bioresource Technology, 2024)

The role of BTG2/PI3K/AKT pathway-mediated microglial activation in T-2 toxin-induced neurotoxicity - Xiukuan Li; Jinyun Long; Chunyan Yao; Xiaoling Liu; Na Li; Yumeng Zhou; Dawei Li; Guiyuan Xiong; Kexue Wang; Yuhui Hao; Ka Chen; Ziyuan Zhou; et al. (Toxicology Letters, 2024)

Resveratrol suppresses liver cancer progression by downregulating AKR1C3: targeting HCC with HSA nanomaterial as a carrier to enhance therapeutic efficacy - Ying Wang; Longxiang Su; Zhansheng Hu; Shuang Peng; Na Li; Haiyan Fu; Baoquan Wang; Huiping Wu (Apoptosis, 2024)

Ti3C2 quantum dots-modified oxygen-vacancy-rich BiOBr hollow microspheres toward optimized photocatalytic performance - Tao Cheng; Zipeng Xing; Na Zhang; Peng Sun; Hui Peng; Zhenzi Li; Nan Wang; Wei Zhou (Chemosphere, 2024)

In vitro generation of trophoblast like stem cells from goat pluripotent stem cells - Qin Na; Siyu Zhang; Peng Shao; Yu Jia; Yanqiu Wang; Mengyi Wei; Yanglin Chen; Chen Chen; Lixia Zhao; Zixin Wang; Yongli Song; Baojiang Wu; et al. (Theriogenology, 2024)

Rational design of a dual-mode fluorescent probe for portable detection of pyriproxyfen in the environment and food - Zhongyong Xu; Qifeng Zheng; Na Li; Weihua Deng; Tianyi Qin; Taoyuze Lv; Lei Wang; Mingle Li; Xiaoqiang Chen; Wenxing Zhang; Bin Liu; Xiaojun Peng (Journal of Hazardous Materials, 2024)

New steroidal saponins from the roots of Paris verticillata - Yang Liu; Na Tang; Xiao-Ying Qian; Tian-Yi Li; Qian Zhang; Peng-Cheng Qiu; Hai-Feng Tang; Yun-Yang Lu; Bang-Le Zhang (Natural Product Research, 2024)

The jasmonate pathway promotes nodule symbiosis and suppresses host plant defense in Medicago truncatula - Da Guo; Jingrui Li; Peng Liu; Yuzhan Wang; Na Cao; Xiangling Fang; Tao Wang; Jiangli Dong (Molecular Plant, 2024)

Macaque Brainnetome Atlas: A multifaceted brain map with parcellation, connection, and histology - Yuheng Lu; Yue Cui; Long Cao; Zhenwei Dong; Luqi Cheng; Wen Wu; Changshuo Wang; Xinyi Liu; Youtong Liu; Baogui Zhang; Deying Li; Bokai Zhao; et al. (Science Bulletin, 2024)

An alkali-extracted neutral heteropolysaccharide from Phellinus nigricans used as an immunopotentiator in immunosuppressed mice by activating macrophages - Feihe Wang; Na Li; Hong Li; Yao Di; Fan Li; Peng Jiang; Guiyun Wang (Carbohydrate Polymers, 2024)

Elucidating the interaction mechanism of rice glutelin and soybean 11S globulin using multi-spectroscopy and molecular dynamics simulation methods - Peng-yu Zhu; Chun-min Ma; Yang Yang; Xin Bian; Li-kun Ren; Bing Wang; Xiao-fei Liu; Feng-lian Chen; Guang Zhang; Na Zhang (Food Chemistry, 2024)

Halogenated aromatic pollutants in routine animal-derived food of south China: Occurrence, sources, and dietary intake risks - Li-Na Zhang; Ping-An Peng; Hui-Ru Li; Ming-Yang Liu; Jian-Fang Hu (Environmental Pollution, 2024)

A small landslide induced a large disaster prior to the heavy rainy season in Jinkouhe, Sichuan, China: characteristics, mechanism, and lessons - Runing Hou; Zhi Li; Weihao Ye; Taixin Peng; Shufeng Tian; Ningsheng Chen; Na Huang; Marcelo Somos-Valenzuela (Landslides, 2024)

Sublethal effect and detoxifying metabolism of metaflumizone and indoxacarb on the fall armyworm, Spodoptera frugiperda - Li Zhang; Hui-Zi Wu; Pei-Yun He; Hai-Qun Cao; Wan-Na Zhang; Ying-Chuan Peng; Cheng-Wang Sheng (Pesticide Biochemistry and Physiology, 2024)

Biotransformation of HBCDs by the microbial communities enriched from mangrove sediments - Fei Yu; Bing Zhang; Yongjin Liu; Wenqi Luo; Haonan Chen; Jun’na Gao; Xueying Ye; Jin Li; Qingyi Xie; Tao Peng; Hui Wang; Tongwang Huang; et al. (Journal of Hazardous Materials, 2024)

Spatiotemporal characteristics of water exchange between the Andaman Sea and the Bay of Bengal - Yihao Wang; Feng Zhou; Xueming Zhu; Ruijie Ye; Yingyu Peng; Zhentao Hu; Haoran Tian; Na Li (Acta Oceanologica Sinica, 2024)

Lignin/mesoporous hollow silica nanosphere thin film nanocomposite loose nanofiltration membrane for dye/salt separation - Qiang Li; Wenge Sun; Bin Shang; Na Zhang; Li Zhao; Huining Deng; Peng Du; Mei Qiao; Jinlong Lu; Zengyu Wang (Desalination, 2024)

Influences of tides on shelf circulation in the northeastern South China Sea during summer - Bingxu Geng; Yeqiang Shu; Jiatang Hu; Shiyu Li; Na Liu; Peng Xiu; Dongxiao Wang (Journal of Marine Systems, 2024)

Prioritization of the ecotoxicological hazard of PAHs towards aquatic species spanning three trophic levels using 2D-QSTR, read-across and machine learning-driven modelling approaches - Feifan Li; Peng Wang; Tengjiao Fan; Na Zhang; Lijiao Zhao; Rugang Zhong; Guohui Sun (Journal of Hazardous Materials, 2024)

Characterization of emopamil binding protein (Cs-ebp) reveals its potential role in cholesterol biosynthesis and growth performance of Chinese tongue sole - Zhangfan Chen; Xihong Li; Peng Cheng; Jiaqi Mai; Yuqi Sun; Jiacheng Wang; Rui Shi; Qi Zhang; Na Wang; Songlin Chen (Aquaculture, 2024)

PLZF protein forms a complex with protein TET1 to target TCF7L2 in undifferentiated spermatogonia - Xiaomin Du; Donghui Yang; Xiuwei Yu; Yudong Wei; Wenbo Chen; Yuanxin Zhai; Fanglin Ma; Mengfei Zhang; Shicheng Wan; Yunxiang Li; Xinchun Yang; Aili Aierken; et al. (Theriogenology, 2024)

Comprehensive assessment of phthalates in indoor dust across China between 2007 and 2019: Benefits from regulatory restrictions - Xiaoqian Li; Na Zheng; Wenhui Zhang; Qirui An; Yining Ji; Changcheng Chen; Sujing Wang; Liyuan Peng (Environmental Pollution, 2024)

3D network of zinc powder woven into fibre filaments for dendrite-free zinc battery anodes - Lin Sha; Bin-Bin Sui; Peng-Fei Wang; Zhe Gong; Yu-Hang Zhang; Yu-Han Wu; Li-Na Zhao; Jun-Jie Tang; Fa-Nian Shi (Chemical Engineering Journal, 2024)

Cuprotosis clusters predict prognosis and immunotherapy response in low-grade glioma - Wenjun Zhu; Ziqi Chen; Min Fu; Qianxia Li; Xin Chen; Xiaoyu Li; Na Luo; Wenhua Tang; Feng Yang; Yiling Zhang; Yuanyuan Zhang; Xiaohong Peng; et al. (Apoptosis, 2024)
Cuprotosis, an emerging mode of cell death, has recently caught the attention of researchers worldwide. However, its impact on low-grade glioma (LGG) patients has not been fully explored. To gain a deeper insight into the relationship between cuprotosis and LGG patients’ prognosis, we conducted this study in which LGG patients were divided into two clusters based on the expression of 18 cuprotosis-related genes. We found that LGG patients in cluster A had better prognosis than those in cluster B. The two clusters also differed in terms of immune cell infiltration and biological functions. Moreover, we identified differentially expressed genes (DEGs) between the two clusters and developed a cuprotosis-related prognostic signature through the least absolute shrinkage and selection operator (LASSO) analysis in the TCGA training cohort. This signature divided LGG patients into high- and low-risk groups, with the high-risk group having significantly shorter overall survival (OS) time than the low-risk group. Its predictive reliability for prognosis in LGG patients was confirmed by the TCGA internal validation cohort, CGGA325 cohort and CGGA693 cohort. Additionally, a nomogram was used to predict the 1-, 3-, and 5-year OS rates of each patient. The analysis of immune checkpoints and tumor mutation burden (TMB) has revealed that individuals belonging to high-risk groups have a greater chance of benefiting from immunotherapy. Functional experiments confirmed that interfering with the signature gene TNFRSF11B inhibited LGG cell proliferation and migration. Overall, this study shed light on the importance of cuprotosis in LGG patient prognosis. The cuprotosis-related prognostic signature is a reliable predictor for patient outcomes and immunotherapeutic response and can help to develop new therapies for LGG.

Activate the filtration capability of 3.5 nm ultra-large pores and eliminate the requirement of pore homogeneity for carbon nanotube array membranes - Na Li; Zemeng Feng; Yiyue He; Zhaogang Peng; Xiangrui Meng; Huijuan Lin; Kui Xu (Desalination, 2024)

Progression of an emission inventory of China integrating CO2 with air pollutants: A chance to learn the influence of development on emissions - Guorui Zhi; Jinhong Du; Aizhong Chen; Wenjing Jin; Na Ying; Zhihui Huang; Peng Xu; Di Wang; Jinghua Ma; Yuzhe Zhang; Jiabao Qu; Hao Zhang; et al. (Atmospheric Environment, 2024)

Response of distributions and emissions of summer biogenic sulfur in the Pacific Arctic to enhanced Pacific Water inflow - Cheng‐Xuan Li; Bao‐Dong Wang; Kan Chen; Gui‐Peng Yang; Jian‐Fang Chen; Li‐Na Lin; Zi‐Cheng Wang (Limnology and Oceanography, 2024)
The inflow of warm and nutrient‐rich Pacific Water (PW) through the Bering Strait into the Arctic Ocean is likely to have far‐reaching consequences for the ecosystem and biogenic sulfur cycle in the Earth's sensitive subarctic–arctic region of the Pacific sector, even impacting climate change under global warming scenarios. We performed a detailed biogeochemical study of summer biogenic sulfur cycling from cold (2012) to warm (2014) years in the Bering Strait and the Chukchi Sea, so as to highlight the importance of enhanced Pacific inflow in driving dimethylsulfide (DMS) variability. In the Bering Strait, the enhanced Pacific inflow led to the vertical expansion of the eastern high‐DMS regions due to the vertical extension of Alaska Coastal Water, and the horizontal expansion of the western surface high‐DMS regions due to the westward intrusion of Bering Shelf Water. The enhanced extension of PW potentially stimulated seawater warming, the northward retreat of the ice edge, and the enlargement of sea ice‐free areas in the Chukchi Sea. The northern ice melting zone at 71°N with a bloom of phytoplankton was an area of locally high dimethylsulfoniopropionate concentrations and slow DMS consumption in 2012. A hotspot for dimethylated sulfur compound concentrations and DMS sea–air flux occurred in the convergence region near 67.7°N during 2014, due to enhanced mixing caused by increased Bering Sea Water. Owing to the increased advection of PW during 2012–2014, surface DMS and its emission to the atmosphere increased sharply by threefold in the Chukchi Sea.

Analysis of the spatial-temporal evolution of Green and low carbon utilization efficiency of agricultural land in China and its influencing factors under the goal of carbon neutralization - Jun Fu; Rui Ding; Yu-qi Zhu; Lin-yu Du; Si-wei Shen; Li-na Peng; Jian Zou; Yu-xuan Hong; Juan Liang; Ke-xin Wang; Wen-qian Xiao (Environmental Research, 2023)

Amino-terminated carbon dots for imaging Golgi apparatus polarity in live cells - Lei Zhan; Peng Hou; Na Chen; Yuan Fang Li; Chun Mei Li; Cheng Zhi Huang (Chemical Engineering Journal, 2023)

ID3 regulates progesterone synthesis in bovine cumulus cells through modulation of mitochondrial function - Zi-Bin Liu; Jia-Bao Zhang; Sheng-Peng Li; Wen-Jie Yu; Na Pei; Hai-Tao Jia; Ze Li; Wen-Fa Lv; Jun Wang; Nam-Hyung Kim; Bao Yuan; Hao Jiang (Theriogenology, 2023)

The immunomodulatory effects of DNA-conjugated collagen scaffolds on bone healing - Jing-han Song; Jun-ting Gu; Gao-peng Dang; Zhi-ting Li; Chen Lei; Ling Li; Zhao Mu; Franklin R. Tay; Kai Jiao; Li-na Niu (Chemical Engineering Journal, 2023)

Constructing branch architectures on fly ash surfaces to immobilize iron tetracarboxy phthalocyanine for synergistic degradation of dye contaminants - Peng Zhang; Na Wei; Jinqiang Wu; Qingyuan Liu; Lianfeng Yang; Shixun Zu; Chunhui Liu; Yun Li; Dapeng Li; Suxiang Ge; Juntao Ma (Journal of Cleaner Production, 2023)

Correction to: Pigmentibacter ruber gen. nov., sp. nov., a novel bacterium of the family Silvanigrellaceae isolated from human blood - Na Peng; Wen Xu; Hai-Min Luo; Peng-Wen Ouyang; Bin Jiang; Zhi-Hua Zhang; You-De Cao; Li-Ming Tan; Ping-Hua Qu; Liang-Yi Xie (Antonie van Leeuwenhoek, 2023)

Quantum neuronal sensing of quantum many-body states on a 61-qubit programmable superconducting processor - Ming Gong; He-Liang Huang; Shiyu Wang; Chu Guo; Shaowei Li; Yulin Wu; Qingling Zhu; Youwei Zhao; Shaojun Guo; Haoran Qian; Yangsen Ye; Chen Zha; et al. (Science Bulletin, 2023)

Identification, in silico selection, and mechanism study of novel antioxidant peptides derived from the rice bran protein hydrolysates - Li-kun Ren; Jing Fan; Yang Yang; Xiao-fei Liu; Bing Wang; Xin Bian; Dang-feng Wang; Yue Xu; Bao-xiang Liu; Peng-yu Zhu; Na Zhang (Food Chemistry, 2023)

Graphene/carbon fiber network constructed by co-carbonization strategy for functional integrated polyimide composites with enhanced electromagnetic shielding and thermal conductive properties - Xiong Li; Tongle Xu; Wenjing Cao; Menghuan Wang; Fengqing Chen; Liyuan Jin; Na Song; Sheng Sun; Peng Ding (Chemical Engineering Journal, 2023)

Lignin-based covalent organic polymers with improved crystallinity for non-targeted analysis of chemical hazards in food samples - Zhan-Chao Li; Wei Li; Rui Wang; Dong-Xia Wang; An-Na Tang; Xiao-Peng Wang; Xiao-Ping Gao; Gai-Ming Zhao; De-Ming Kong (Journal of Hazardous Materials, 2023)

The role of MAPK/NF-κB-associated microglial activation in T-2 toxin-induced mouse learning and memory impairment - Na Li; Chun-Yan Yao; Jun Diao; Xiao-Ling Liu; En-Jie Tang; Qing-Song Huang; Yu-Meng Zhou; Yue-Gu Hu; Xiu-Kuan Li; Jin-Yun Long; Hua Xiao; Da-Wei Li; et al. (Food and Chemical Toxicology, 2023)

A record-breaking extreme heat event caused unprecedented warming of lakes in China - Weijia Wang; Kun Shi; Xiwen Wang; Siqi Wang; Dong Zhang; Yuanyuan Peng; Na Li; Yunlin Zhang; Yibo Zhang; Boqiang Qin; R. Iestyn Woolway; Erik Jeppesen (Science Bulletin, 2023)

A multispectral method for retrieving overlapping cloud top heights from passive radiometers - Shiwen Teng; Chao Liu; Zhonghui Tan; Jiming Li; Na Xu; Xiuqing Hu; Peng Zhang; Wei Yan; Byung-Ju Sohn (Remote Sensing of Environment, 2023)

Application of a novel and green temperature-responsive deep eutectic solvent system to simultaneously extract and separate different polar active phytochemicals from Schisandra chinensis (Turcz.) Baill - Xin-Yu Yan; Zi-Hui Cai; Peng-Quan Zhao; Jian-Dong Wang; Li-Na Fu; Qi Gu; Yu-Jie Fu (Food Research International, 2023)

Analysis of PAT1 subfamily members in the GRAS family of upland cotton and functional characterization of GhSCL13-2A in Verticillium dahliae resistance - Chen Chen; Li-Li Lu; Shu-Ya Ma; Yan-Peng Zhao; Na Wu; Wen-Jie Li; Li Ma; Xian-Hui Kong; Zong-Ming Xie; Yu-Xia Hou (Plant Cell Reports, 2023)

Effect of grazing exclusion on emission of greenhouse gases and soil organic carbon turnover in alpine shrub meadow - Zhiqiang Dang; Na Guo; Shanshan Li; A. Allan Degen; Jingjuan Cao; Bin Deng; Aidong Wang; Zhen Peng; Luming Ding; Ruijun Long; Zhanhuan Shang (Science of The Total Environment, 2023)

Enrofloxacin-induced transfer of multiple-antibiotic resistance genes and emergence of novel resistant bacteria in red swamp crayfish guts and pond sediments - Xuexia Jin; Sizhen Liu; Zhenting Zhang; Tong Liu; Na Li; Yunxiang Liang; Jinshui Zheng; Nan Peng (Journal of Hazardous Materials, 2023)

Modulations in protein phosphorylation explain the physiological responses of barley (Hordeum vulgare) to nanoplastics and ZnO nanoparticles - Junhong Guo; Shuxin Li; Marian Brestic; Na Li; Peng Zhang; Lei Liu; Xiangnan Li (Journal of Hazardous Materials, 2023)

Effects of fine ambient particulate matters on de novo hypertensive disorders of pregnancy and blood pressure before 20 weeks - Zhichao Yuan; Qin Li; Tao Su; Jie Yang; Junjun Chen; Yuanzhou Peng; Shuang Zhou; Heling Bao; Shusheng Luo; Hui Wang; Jue Liu; Na Han; et al. (Environmental Research, 2023)

IFI44L as a novel epigenetic silencing tumor suppressor promotes apoptosis through JAK/STAT1 pathway during lung carcinogenesis - Yong Zeng; Hong-qiang Chen; Zhe Zhang; Jun Fan; Jing-zhi Li; Shi-meng Zhou; Na Wang; Su-peng Yan; Jia Cao; Jin-yi Liu; Zi-yuan Zhou; Wen-bin Liu (Environmental Pollution, 2023)

A green and designable natural deep eutectic solvent-based supramolecular solvents system: Efficient extraction and enrichment for phytochemicals - Zi-Hui Cai; Jian-Dong Wang; Lin Liu; Liu-Ding Ruan; Qi Gu; Xin-Yu Yan; Li-Na Fu; Peng-Quan Zhao; Su Zhang; Yu-Jie Fu (Chemical Engineering Journal, 2023)

Ecotoxicological QSAR modelling of the acute toxicity of fused and non-fused polycyclic aromatic hydrocarbons (FNFPAHs) against two aquatic organisms: Consensus modelling and comparison with ECOSAR - Feifan Li; Guohui Sun; Tengjiao Fan; Na Zhang; Lijiao Zhao; Rugang Zhong; Yongzhen Peng (Aquatic Toxicology, 2023)

Association between ambient carbon monoxide levels and hospitalization costs of patients with myocardial infarction: Potential effect modification by ABO blood group - Qing-Song Huang; Lai-Xin Zhou; Li-Li Yang; Yue-Xu Jiang; Hua Xiao; Da-Wei Li; Yu-Meng Zhou; Yue-Gu Hu; Na Li; Ya-Fei Li; Ai-Ling Ji; Peng Luo; et al. (Environmental Research, 2023)

Roles of microRNAs and exosomes in Helicobacter pylori associated gastric cancer - Xiao-Han Xu; Shu-Li Shao; Dong Guo; Li-Na Ge; Zan Wang; Peng Liu; Yuan-Yong Tao (Molecular Biology Reports, 2023)

Does aspirin reduce the incidence, recurrence, and mortality of hepatocellular carcinoma? A GRADE-assessed systematic review and dose–response meta-analysis - Shaodi Ma; Guangbo Qu; Chenyu Sun; Haixia Liu; Yuemeng Jiang; Ning Li; Birong Wu; Juan Gao; Linya Feng; Peng Xie; Weihang Xia; Na Hyun Kim; et al. (European Journal of Clinical Pharmacology, 2023)

Genome-wide identification of calcium-dependent protein kinases (CDPKs) in pear (Pyrus bretschneideri Rehd) and characterization of their responses to Venturia nashicola infection - Shaohua Liu; Junhao Li; Na Li; Peng Zhou; Liulin Li (Horticulture, Environment, and Biotechnology, 2022)

New polymerized sesquiterpene lactones from Ainsliaea yunnanensis and their activity evaluation - Na Zhou; Jin-Jie Li; Yong Wu; Ze-Yu Wang; Xin Wang; Zhi-Peng Yin; Xin-Peng Wang; Yi-Ran Liu; Xiao-Ya Shang (Natural Product Research, 2022)

Phylogenetic analyses, morphological studies, and muscarine detection reveal two new toxic Pseudosperma (Inocybaceae, Agaricales) species from tropical China - Li-Na Zhao; Wen-Jie Yu; Lun-Sha Deng; Jian-Hua Hu; Yu-Peng Ge; Nian-Kai Zeng; Yu-Guang Fan (Mycological Progress, 2022)

p-Nitrophenol contaminated soil remediation in a spray-type coaxial cylindrical dielectric barrier discharge plasma system - Nan Jiang; Ying Qu; Zheng Yu; Bangfa Peng; Jie Li; Kefeng Shang; Na Lu; Yan Wu (Environmental Science and Pollution Research, 2022)

Why empresses have more sons? Maternal instant social condition determines it - Yan-Peng Li; Wei Ding; Zhi-Pang Huang; Ru-Liang Pan; Na Li; Guo-Peng Ren; Liang-Wei Cui; Qing-hua Cai; Wen Xiao (Behavioral Ecology and Sociobiology, 2022)
Sexual selection echoed by the sex ratio is a critical issue in evolution and reproductive biology studies, and the second sex ratio (sex ratio at birth, SRB) is an important evaluation indicator for sex regulation. However, broad debates on sex ratio at birth exist due to the lack of a clear spatiotemporal genealogical database. This study explicitly tests the Trivers and Willard’s hypothesis stating that parents with good social conditions tend to show a male-biased SRB. Using a database of Chinese imperial families from 211BC to 1912 (2142 years) which avoids the spatiotemporal confusion of data thanks to its clear boundaries and long timespan, we found that a proportion of males at birth was 0.54. In particular, the results indicate that the empresses generated a significantly higher male-biased SRB than the concubines within the imperial harems (0.61 vs 0.53), while the SRB of concubines was not higher than ordinary people (0.53 vs 0.52). A significant difference of SRB before and after empress coronation (0.48 vs 0.65) was detected, indicating that the change to a higher social status is the leading cause of a biased SRB. These findings suggest that mothers with privileged instant social conditions tend to generate more boys than girls. In other words, a higher maternal social rank during the conception period, instead of rich resources, forms the primary mechanism regulating the SRB. Significance statement Adaptive sex ratio has been a debatable topic difficult to clearly verify since the publication of Trivers and Willard Hypothesis in 1973, which proposes that parents who have good conditions should produce more male offspring. The one reason is that the validity and sample size of the databases used contained unavoidable confounding noise, both genealogically and genetically. To overcome these issues, we specifically compiled a historical database of Chinese imperial families, which are characterized by a confined mating harem and unique eunuch system, guaranteeing biological and genetic purity with precise genealogical relationships and genetic linkages between the parents and the offspring. Thus, this is an extraordinary effort to clarify the hypotheses proposed by TWH and other hypotheses.

MdMYB88/124 modulates apple tree microRNA biogenesis through post-transcription processing and/or transcription pathway - Chun-dong Niu; Huan-ran Shi; Zi-tong Zhang; Tian-le Fan; Huan Dang; Peng-xiang Chen; Yin-peng Xie; Cha-na Bao; Feng-wang Ma; Qing-mei Guan; Xue-wei Li (Acta Physiologiae Plantarum, 2022)

Total, bioavailable and free 25-hydroxyvitamin D are associated with the prognosis of patients with non-small cell lung cancer - Si-Min Peng; Na Yu; Jun Che; Jia-Ying Xu; Guo-Chong Chen; Da-Peng Li; Yu-Song Zhang; Li-Qiang Qin (Cancer Causes & Control, 2022)

Anti-inflammatory and antioxidant activities of chemical constituents from the flower buds of Buddleja officinalis - Fei-Bing Huang; Na Liang; Nusrat Hussain; Xu-Dong Zhou; Muhammad Ismail; Qing-Ling Xie; Huang-He Yu; Yu-Qing Jian; Cai-Yun Peng; Bin Li; Bin Liu; Sheng-Huang Chen; et al. (Natural Product Research, 2022)

Secoiridoid glycosides from the fruits of Cornus officinalis - Xin Wang; Xiang-Jian Zhong; Na Zhou; Lin-Lin Ji; Jin-Jie Li; Ning Cai; Qing-Bo Wang; Peng-Cheng Lin; Xiao-Ya Shang (Natural Product Research, 2022)

The Mechanism of Stem Cell Aging - Liangyu Mi; Junping Hu; Na Li; Jinfang Gao; Rongxiu Huo; Xinyue Peng; Na Zhang; Ying Liu; Hanxi Zhao; Ruiling Liu; Liyun Zhang; Ke Xu (Stem Cell Reviews and Reports, 2022)
Stem cells have self-renewal ability and multi-directional differentiation potential. They have tissue repair capabilities and are essential for maintaining the tissue homeostasis. The depletion of stem cells is closely related to the occurrence of body aging and aging-related diseases. Therefore, revealing the molecular mechanisms of stem cell aging will set new directions for the therapeutic application of stem cells, the study of aging mechanisms, and the prevention and treatment of aging-related diseases. This review comprehensively describes the molecular mechanisms related to stem cell aging and provides the basis for further investigations aimed at developing new anti-stem cell aging strategies and promoting the clinical application of stem cells.

Corrigendum: Pigmentibacter ruber gen. nov., sp. nov., a novel bacterium of the family Silvanigrellaceae isolated from human blood - Na Peng; Wen Xu; Hai-Min Luo; Peng-Wen Ouyang; Bin Jiang; Zhi-Hua Zhang; You-De Cao; Li-Ming Tan; Ping-Hua Qu; Liang-Yi Xie (Antonie van Leeuwenhoek, 2022)

Cancer metabolism and tumor microenvironment: fostering each other? - Yiyuan Yuan; Huimin Li; Wang Pu; Leilei Chen; Dong Guo; Hongfei Jiang; Bo He; Siyuan Qin; Kui Wang; Na Li; Jingwei Feng; Jing Wen; et al. (Science China Life Sciences, 2022)

The in vitro and in vivo anti-inflammatory activities of triterpene saponins from Clematis florida - Na-Na Yang; Yi-Fan Zhang; Hai-Tao Zhang; Xin-Hua Ma; Jin-Huang Shen; Peng Li; Tian-Hua Zhong; Yong-Hong Zhang (Natural Product Research, 2021)

Alkaloids with acetylcholinesterase inhibitory activity from Corydalis racemosa (Thunb.) Pers - Hui-Na Yao; Zhi-Tian Peng; Yun-Feng Zhang; Di-Fa Liu; Bing-Feng Huang; Peng-Fei Tu; Yun-Fang Zhao; Hui-Xia Huo; Jun Li (Natural Product Research, 2021)

1,4-Dioxane Degradation Performance of Tetrahydrofuran-Grown Arthrobacter sp. WN18 - Peng Wang; Tingchen Cui; Jialu Li; Na Liu; Mei Hong (Water, Air, & Soil Pollution, 2021)

Sinanaerobacter chloroacetimidivorans gen. nov., sp. nov., an obligate anaerobic bacterium isolated from anaerobic sludge - Yixuan Bao; Junwei Liu; Xuan Zhang; Peng Lei; Jiguo Qiu; Jian He; Na Li (Antonie van Leeuwenhoek, 2021)

Influence of elevation on bioregionalisation: A case study of the Sino‐Himalayan flora - Yun Liu; Jian‐Fei Ye; Hai‐Hua Hu; Dan‐Xiao Peng; Li‐Na Zhao; Li‐Min Lu; Wajid Zaman; Zhi‐Duan Chen (Journal of Biogeography, 2021)
Aim Elevation is an important factor that influences bioregionalisation in mountainous areas, but its effects are not well known. Taking the Sino‐Himalayan flora as a case, we aimed to test the effect of elevation on bioregionalisation and provide a regionalisation scheme of the Sino‐Himalayan flora. Location The Sino‐Himalaya (East Himalaya, the Hengduan Mountains and the Yunnan Plateau in China). Taxon Angiosperms. Methods We compiled distribution data and elevation ranges of angiosperms in the Sino‐Himalaya and adjacent areas and reconstructed a species‐level phylogenetic tree of 19,313 angiosperm species. The area was divided into 398 grid cells, each 1 × 1°. Nine datasets of different elevation ranges were then used to delineate the flora of the Sino‐Himalaya and adjacent areas using the phylogenetic dissimilarity approach. Results A comparison of nine regionalisation schemes of the Sino‐Himalayan flora based on different elevation range datasets revealed that more than half of grid cells were allocated to more than one subregion. Most of these grid cells were located in areas with a wide range of elevation and/or at the boundaries between subregions. After revising the subregion allocations of eight shifting grid cells, we generated a phylogeny‐ and elevation‐based regionalisation scheme of three regions, comprising eight subregions, for the Sino‐Himalayan flora. Main conclusions By integrating phylogenetic and elevational information, the Sino‐Himalaya can be divided into three floristic regions: the Yunnan Plateau region, the Hengduan Mountains region and the East Himalaya region. Our study provides novel insights into the regionalisation of the flora and highlights the importance of incorporating elevation data in the bioregionalisation of areas with a broad elevational range.

Astragaloside IV inhibits adriamycin-induced cardiac ferroptosis by enhancing Nrf2 signaling - Li-Fei Luo; Peng Guan; Lu-Yun Qin; Jian-Xin Wang; Na Wang; En-Sheng Ji (Molecular and Cellular Biochemistry, 2021)

Tritonibacter aquimaris sp. nov. and Tritonibacter litoralis sp. nov., two novel members of the Roseobacter group isolated from coastal seawater - Na Li; Xiao-yan He; Ning-hua Liu; Tie-ji Gu; Jian Li; Yu-hui Geng; Shan Zhang; Peng Wang; Hui-hui Fu; Mei Shi; Xiu-lan Chen; Yu-zhong Zhang; et al. (Antonie van Leeuwenhoek, 2021)

Pigmentibacter ruber gen. nov., sp. nov., a novel bacterium of the family Silvanigrellaceae isolated from human blood - Na Peng; Wen Xu; Hai-Min Luo; Peng-Wen Ouyang; Bin Jiang; Zhi-Hua Zhang; You-De Cao; Li-Ming Tan; Ping-Hua Qu; Liang-Yi Xie (Antonie van Leeuwenhoek, 2021)

Chronic stress promotes acute myeloid leukemia progression through HMGB1/NLRP3/IL-1β signaling pathway - Na Liu; Yifan Wu; Xin Wen; Peng Li; Fei Lu; Hong Shang (Journal of Molecular Medicine, 2021)

7,8-Dihydroxyflavone Alleviates Anxiety-Like Behavior Induced by Chronic Alcohol Exposure in Mice Involving Tropomyosin-Related Kinase B in the Amygdala - Na Wang; Xing Liu; Xin-Tong Li; Xin-Xin Li; Wei Ma; Yan-Min Xu; Yong Liu; Qing Gao; Tao Yang; Hongxuan Wang; Ying Peng; Xiao-Feng Zhu; et al. (Molecular Neurobiology, 2021)

Correction to: CCR2 and CCR5 promote diclofenac-induced hepatotoxicity in mice - Zhanke He; Guoquan Wei; Na Li; Mengwei Niu; Shenhai Gong; Guangyan Wu; Teng Wang; Yong Jiang; Peng Chen (Naunyn-Schmiedeberg's Archives of Pharmacology, 2020)

Colletotrichum neorubicola sp. nov., a new leaf anthracnose pathogen of raspberry from northeast China - Li-Ping Liu; Yu Wang; Peng-Lei Qiu; Bo Zhang; Lin Zhang; Na Wang; Yu Li; Jie Gao; Tom Hsiang (Mycological Progress, 2020)

Benzophenone glycosides from the pericarps of Aquilaria yunnanensis S. C. Huang - Hui Sun; Yun-Feng Zhang; Hui-Xia Huo; Peng-Wei Guan; Chao-Chao Wang; Hui-Na Yao; Yun-Fang Zhao; Peng-Fei Tu; Jun Li (Natural Product Research, 2020)

Preparation of Novel ALRCs/nZVI Composite and Its Removal of Cr(VI) from Aqueous - Xuan Zhang; Xiao-qiang Cao; Guang Li; Jijie Yin; Di Zhang; Mingzhen Li; Na Meng; Liang Dong; Xian-jun Lyu; Lin Li; Jun Qiu; Yan Zhang; et al. (International Journal of Environmental Research, 2020)

Scorpion Venom Heat-Resistant Peptide is Neuroprotective against Cerebral Ischemia-Reperfusion Injury in Association with the NMDA-MAPK Pathway - Xu-Gang Wang; Dan-Dan Zhu; Na Li; Yue-Lin Huang; Ying-Zi Wang; Ting Zhang; Chen-Mei Wang; Bin Wang; Yan Peng; Bi-Ying Ge; Shao Li; Jie Zhao (Neuroscience Bulletin, 2020)

Transient Receptor Potential Ankyrin 1 Contributes to Lysophosphatidylcholine-Induced Intracellular Calcium Regulation and THP-1-Derived Macrophage Activation - Chao Tian; Rongqi Huang; Feng Tang; Zuoxian Lin; Na Cheng; Xiaobo Han; Shuai Li; Peng Zhou; Sihao Deng; Hualin Huang; Huifang Zhao; Junjie Xu; et al. (The Journal of Membrane Biology, 2020)

Risks of maternal prepregnancy overweight/obesity, excessive gestational weight gain, and bottle-feeding in infancy rapid weight gain: evidence from a cohort study in China - Shaoping Yang; Hong Mei; Hui Mei; Yan Yang; Na Li; Yafei Tan; Yiming Zhang; Dan Zhang; Yan Zhang; An’na Peng; Bin Zhang (Science China Life Sciences, 2019)

Elevated insulin levels compromise endometrial decidualization in mice with decrease in uterine apoptosis in early-stage pregnancy - Chen Zhang; Chengshun Yang; Na Li; Xueqing Liu; Junlin He; Xuemei Chen; Yubin Ding; Chao Tong; Chuan Peng; Hubin Yin; Yingxiong Wang; Rufei Gao (Archives of Toxicology, 2019)

A structured approach to the analysis of remote sensing images - Donghui Yan; Congcong Li; Na Cong; Le Yu; Peng Gong (International Journal of Remote Sensing, 2019)

rTMS combined with motor training changed the inter-hemispheric lateralization - Jing-na Jin; Xin Wang; Ying Li; He Wang; Zhi-peng Liu; Tao Yin (Experimental Brain Research, 2019)

Joint toxicity of six common heavy metals to Chlorella pyrenoidosa - Ling-Yun Mo; Dan-Na Zhao; Meng Qin; Li-Tang Qin; Hong-Hu Zeng; Yan-Peng Liang (Environmental Science and Pollution Research, 2019)

Seminal Plasma Exosomes: Promising Biomarkers for Identification of Male and Pseudo-Males in Cynoglossus semilaevis - Bo Zhang; Na Zhao; Lei Jia; Kang Peng; Jinyuan Che; Kunming Li; Xiaoxu He; Jinsheng Sun; Baolong Bao (Marine Biotechnology, 2019)

CCR2 and CCR5 promote diclofenac-induced hepatotoxicity in mice - Zhanke He; Guoquan Wei; Na Li; Mengwei Niu; Shenhai Gong; Guangyan Wu; Teng Wang; Yong Jiang; Peng Chen (Naunyn-Schmiedeberg's Archives of Pharmacology, 2019)

Two new polyketides from the fungus Penicillium oxalicum MHZ153 - Yi Ren; Ling-Hui Chao; Jing Sun; Xiao-Nan Chen; Hui-Na Yao; Zhi-Xiang Zhu; Dan Dong; Ting Liu; Peng-Fei Tu; Jun Li (Natural Product Research, 2019)

sEMG Based Gait Phase Recognition for Children with Spastic Cerebral Palsy - Peng-na Wei; Rongfu Xie; Rongnian Tang; Chuang Li; Janis Kim; Ming Wu (Annals of Biomedical Engineering, 2019)

HNMDA: heterogeneous network-based miRNA–disease association prediction - Li-Hong Peng; Chuan-Neng Sun; Na-Na Guan; Jian-Qiang Li; Xing Chen (Molecular Genetics and Genomics, 2018)

Establishment and characterization of a kidney cell line from kelp grouper Epinephelus moara - Xiao-Feng Liu; Ya-Hong Wu; Shi-Na Wei; Na Wang; Peng-Fei Li; Yang-Zhen Li; Nian-Wei Zhang; Qi-Wei Qin; Song-Lin Chen (Fish Physiology and Biochemistry, 2018)

Gender-Related Hippocampal Proteomics Study from Young Rats After Chronic Unpredicted Mild Stress Exposure - Lin-Na Ning; Teng Zhang; Jiang Chu; Na Qu; Li Lin; Ying-Yan Fang; Yan Shi; Peng Zeng; Er-Li Cai; Xiao-Ming Wang; Qun Wang; You-Ming Lu; et al. (Molecular Neurobiology, 2018)

Physiological and transcriptional analysis reveals pathways involved in iron deficiency chlorosis in fragrant citrus - Long-Fei Jin; Yong-Zhong Liu; Wei Du; Li-Na Fu; Syed Bilal Hussain; Shu-Ang Peng (Tree Genetics & Genomes, 2017)

Tissue-Specific Regulation of the Contents and Correlations of Mineral Elements in Hens by Zinc Oxide Nanoparticles - Yong Zhao; Yan-Ni Feng; Lan Li; Hong-Fu Zhang; Yu-Na Zhang; Peng-Fei Zhang; Xin-Qi Liu; Wei-Dong Zhang; Ting-Ting Huang; Li Zhao; Wei Shen; Zhi-Hui Hao (Biological Trace Element Research, 2017)

A Point Mutation in SCN1A 5′ Genomic Region Decreases the Promoter Activity and Is Associated with Mild Epilepsy and Seizure Aggravation Induced by Antiepileptic Drug - Qu-Wen Gao; Li-Dong Hua; Jie Wang; Cui-Xia Fan; Wei-Yi Deng; Bin Li; Wen-Jun Bian; Chuan-Xing Shao; Na He; Peng Zhou; Wei-Ping Liao; Yi-Wu Shi (Molecular Neurobiology, 2017)

Activation of group I metabotropic glutamate receptors regulates the excitability of rat retinal ganglion cells by suppressing Kir and I h - Qian Li; Peng Cui; Yanying Miao; Feng Gao; Xue-Yan Li; Wen-Jing Qian; Shu-Xia Jiang; Na Wu; Xing-Huai Sun; Zhongfeng Wang (Brain Structure and Function, 2017)

Effects of yeast products on the intestinal morphology, barrier function, cytokine expression, and antioxidant system of weaned piglets - Huan-sheng Yang; Fei Wu; Li-na Long; Tie-jun Li; Xia Xiong; Peng Liao; Hong-nan Liu; Yu-long Yin (Journal of Zhejiang University-SCIENCE B, 2016)

Sirtuin-3 (SIRT3) protects pancreatic β-cells from endoplasmic reticulum (ER) stress-induced apoptosis and dysfunction - Hao-Hao Zhang; Xiao-Jun Ma; Li-Na Wu; Yan-Yan Zhao; Peng-Yu Zhang; Ying-Hui Zhang; Ming-Wei Shao; Fei Liu; Fei Li; Gui-Jun Qin (Molecular and Cellular Biochemistry, 2016)

Globular CTRP9 inhibits oxLDL-induced inflammatory response in RAW 264.7 macrophages via AMPK activation - Peng Zhang; Chengmin Huang; Jun Li; Tingting Li; Haipeng Guo; Tianjiao Liu; Na Li; Qing Zhu; Yuan Guo (Molecular and Cellular Biochemistry, 2016)

High prevalence and diversity of viruses of the subfamily Gammaherpesvirinae, family Herpesviridae, in fecal specimens from bats of different species in southern China - Xue-yan Zheng; Min Qiu; Shao-wei Chen; Jian-peng Xiao; Li-zhen Ma; Shan Liu; Jun-hua Zhou; Qiong-hua Zhang; Xing Li; Zhong Chen; Yi Wu; Hui-fang Chen; et al. (Archives of Virology, 2016)

Narciclasine, a potential allelochemical, affects subcellular trafficking of auxin transporter proteins and actin cytoskeleton dynamics in Arabidopsis roots - Yanfeng Hu; Xiaofan Na; Jiaolong Li; Lijing Yang; Jia You; Xiaolei Liang; Jianfeng Wang; Liang Peng; Yurong Bi (Planta, 2015)

Clinical, biochemical, neuroimaging and molecular findings of X-linked Adrenoleukodystrophy patients in South China - Min-yan Jiang; Yan-na Cai; Cui-li Liang; Min-zhi Peng; Hui-ying Sheng; Li-ping Fan; Rui-zhu Lin; Hua Jiang; Yonglan Huang; Li Liu (Metabolic Brain Disease, 2015)

Analyzing nonlinear variations in terrestrial vegetation in China during 1982–2012 - Yanxu Liu; Xianfeng Liu; Yi’na Hu; Shuangshuang Li; Jian Peng; Yanglin Wang (Environmental Monitoring and Assessment, 2015)

Expression of the Lymphocyte Chemokine XCL1 in Lung Tissue of COPD Mice, and Its Relationship to CD4+/CD8+ Ratio and IL-2 - Songming Zhuo; Na Li; Yi Zheng; Xiao Peng; Anying Xu; Yun Ge (Cell Biochemistry and Biophysics, 2015)

HPLC simultaneous determination of arbutin, chlorogenic acid and 6′- O -caffeoylarbutin in different parts of Vaccinium dunalianum Wight - Xu-Lu Luo; Na Li; Min Xu; Hong-Tao Zhu; Peng He; Yong Ding; Ping Zhao; Ying-Jun Zhang (Natural Product Research, 2015)

Reproductive management through integration of PGD and MPS-based noninvasive prenatal screening/diagnosis for a family with GJB2-associated hearing impairment - WenPing Xiong; DaYong Wang; Yuan Gao; Ya Gao; HongYang Wang; Jing Guan; Lan Lan; JunHao Yan; Liang Zong; Yuan Yuan; Wei Dong; SeXin Huang; et al. (Science China Life Sciences, 2015)

Isolation of differentially expressed sex genes in garden asparagus using suppression subtractive hybridization - Chuan-liang Deng; Ning-na Wang; Shu-fen Li; Tian-yu Dong; Xin-peng Zhao; Shao-jing Wang; Wu-jun Gao; Long-dou Lu (Journal of Plant Research, 2015)

Identification of landslide spatial distribution and susceptibility assessment in relation to topography in the Xi’an Region, Shaanxi Province, China - Jianqi Zhuang; Jianbing Peng; Javed Iqbal; Tieming Liu; Na Liu; Yazhe Li; Penghui Ma (Frontiers of Earth Science, 2015)

Modeling dissolved organic carbon and carbon export in the equatorial Pacific Ocean - Na Liu; Lili Zeng; Yizhen Li; Peng Xiu (Geo-Marine Letters, 2015)

Synthesis and in vitro antiproliferative activity of novel benzisoselenazolone derivatives - Li-na Xuan; Peng Wang; Kai Zhang; Yan-ping Shi; Yu-ming Liu; Tao Zhu; Bao-quan Chen (Medicinal Chemistry Research, 2015)

Inactivation of FoxM1 transcription factor contributes to curcumin-induced inhibition of survival, angiogenesis, and chemosensitivity in acute myeloid leukemia cells - Jing-ru Zhang; Fei Lu; Ting Lu; Wen-hao Dong; Peng Li; Na Liu; Dao-xin Ma; Chun-yan Ji (Journal of Molecular Medicine, 2014)

Promoter hypermethylation may be an important mechanism of the transcriptional inactivation of ARRDC3, GATA5, and ELP3 in invasive ductal breast carcinoma - Da Wang; Peng-Na Yang; Jin Chen; Xian-Yao Zhou; Qiu-Jun Liu; Hong-Jiang Li; Chang-Long Li (Molecular and Cellular Biochemistry, 2014)

Involvement of calcium-sensing receptors in hypoxia-induced vascular remodeling and pulmonary hypertension by promoting phenotypic modulation of small pulmonary arteries - Xue Peng; Hong-Xia Li; Hong-Jiang Shao; Guang-Wei Li; Jian Sun; Yu-Hui Xi; Hong-Zhu Li; Xin-Yan Wang; Li-Na Wang; Shu-Zhi Bai; Wei-Hua Zhang; Li Zhang; et al. (Molecular and Cellular Biochemistry, 2014)

Meta-discoveries from a synthesis of satellite-based land-cover mapping research - Le Yu; Lu Liang; Jie Wang; Yuanyuan Zhao; Qu Cheng; Luanyun Hu; Shuang Liu; Liang Yu; Xiaoyi Wang; Peng Zhu; Xueyan Li; Yue Xu; et al. (International Journal of Remote Sensing, 2014)

Synthesis, biological evaluation, and molecular docking studies of pyrazolyl-acylhydrazone derivatives as novel anticancer agents - Man Xing; Ting-Ting Zhao; Yu-Jia Ren; Na-Na Peng; Xian-Hui Yang; Xi Li; Hui Zhang; Gao-Qi Liu; Li-Rong Zhang; Hai-Liang Zhu (Medicinal Chemistry Research, 2014)

M3 mAChR-mediated IL-8 expression through PKC/NF-κB signaling pathways - Zu-Peng Xu; Yun Song; Kai Yang; Wei Zhou; Li-Na Hou; Liang Zhu; Hong-Zhuan Chen; Yong-Yao Cui (Inflammation Research, 2014)

Breast Cancer Resistance Protein-Mediated Efflux of Luteolin Glucuronides in HeLa Cells Overexpressing UDP-Glucuronosyltransferase 1A9 - Lan Tang; Ye Li; Wei-Ying Chen; Shan Zeng; Ling-Na Dong; Xiao-Juan Peng; Wen Jiang; Ming Hu; Zhong-Qiu Liu (Pharmaceutical Research, 2014)

Infection of Prions and Treatment of PrP106–126 Alter the Endogenous Status of Protein 14-3-3 and Trigger the Mitochondrial Apoptosis Possibly via Activating Bax Pathway - Qi Shi; Qin-Qin Song; Peng Sun; Jin Zhang; Juan Song; Li-Na Chen; Kang Xiao; Shao-Bin Wang; Ya-Zhou Zhang; Gong-Qi Li; Lin-Jun Sheng; Bao-Dong Wang; et al. (Molecular Neurobiology, 2014)

Quantifying interactions between propranolol and dissolved organic matter (DOM) from different sources using fluorescence spectroscopy - Na Peng; Kaifeng Wang; Guoguang Liu; Fuhua Li; Kun Yao; Wenying Lv (Environmental Science and Pollution Research, 2014)

A theoretical study on the mechanism of a superficial mutation inhibiting the enzymatic activity of CYP1A2 - Li-Na Ma; Zhen-Zhen Du; Peng Lian; Dong-Qing Wei (Interdisciplinary Sciences: Computational Life Sciences, 2014)

Molecular phylogeny and genetic variation in the genus Lilium native to China based on the internal transcribed spacer sequences of nuclear ribosomal DNA - Yun-peng Du; Heng-bin He; Zhong-xuan Wang; Shuang Li; Chi Wei; Xiao-na Yuan; Qi Cui; Gui-xia Jia (Journal of Plant Research, 2014)

Multiple attenuation using λ-f domain high-resolution Radon transform - Zhi-Na Li; Zhen-Chun Li; Peng Wang; Qiang Xu (Applied Geophysics, 2013)

Genes encoding the production of extracellular polysaccharide bioflocculant are clustered on a 30-kb DNA segment in Bacillus licheniformis - Shan Yan; Na Wang; Zhen Chen; Yuanpeng Wang; Ning He; Yajuan Peng; Qingbiao Li; Xu Deng (Functional & Integrative Genomics, 2013)

Down-regulation of DNA methyltransferase 3B in staurosporine-induced apoptosis and its mechanism in human hepatocarcinoma cell lines - Chao Zhao; Peng Yin; Chuanzhong Mei; Na Li; Wantong Yao; Xin Li; Jingjing Qi; Kun Fan; Zengxia Li; Liying Wang; Yinghong Shi; Shuangjian Qiu; et al. (Molecular and Cellular Biochemistry, 2013)

Molecular characterization of influenza B viruses isolated in east-central China in 2009–2010 - Na Zhu; Peng Li; Jingfeng Yu; Yongdong Li; Jiuru Zhao; Han Xia; Shuang Tang; Zhong Zhang; Zheng Kou; Shiyu Yin; Zhaojun Fan; Tianxian Li (Virus Genes, 2013)

Structure and evolution of the mitochondrial genome of Exorista sorbillans: the Tachinidae (Diptera: Calyptratae) perspective - Yuan-jun Shao; Xian-qiong Hu; Guang-da Peng; Rui-xian Wang; Rui-na Gao; Chao Lin; Wei-de Shen; Rui Li; Bing Li (Molecular Biology Reports, 2012)

Synthesis, crystal structure and biological activity of novel anthranilic diamide insecticide containing alkyl ether group - Yu Zhao; Li-ping Xu; Jun Tong; Yong-qiang Li; Li-xia Xiong; Fang Li; Li-na Peng; Zheng-ming Li (Molecular Diversity, 2012)

Crucial physical characteristics of sea ice in the Arctic section of 143°–180°W during August and early September 2008 - Ruibo Lei; Zhijun Li; Na Li; Peng Lu; Bin Cheng (Acta Oceanologica Sinica, 2012)

Association between TaqIB polymorphism of cholesteryl ester transfer protein and coronary artery disease in the Chinese population - Qi Yu; En-qi Liu; Si-hai Zhao; Ya-feng Li; Yan-li Wang; Yu-long Chen; Ke-na Wei; Bing-qiao Huang; Jian-lin Fan; Peng-hui Yang (Journal of Zhejiang University-SCIENCE B, 2012)

Fluorofenidone attenuates renal interstitial fibrosis in the rat model of obstructive nephropathy - Bing-xin Li; Yi-ting Tang; Wei Wang; Yan-yun Xie; Na-sui Wang; Qiong-jing Yuan; Fang-fang Zhang; Zhang-zhe Peng; Gao-yun Hu; Li-jian Tao (Molecular and Cellular Biochemistry, 2011)

IL-6 −174G>C polymorphism and cancer risk: a meta-analysis involving 29,377 cases and 37,739 controls - Bin Xu; Xiao-Bing Niu; Zi-Dun Wang; Wei Cheng; Na Tong; Yuan-Yuan Mi; Zhi-Chao Min; Jun Tao; Peng-Chao Li; Wei Zhang; Hong-Fei Wu; Zheng-Dong Zhang; et al. (Molecular Biology Reports, 2011)

A Sandwiched Biological Fluorescent Probe for the Diagnosis of Human Ovarian Tumor Based on TiO2 Nanoparticles - Peisi Zhu; Shasheng Huang; Mengyao Li; Na Ding; Bing Peng; Lingmi Kong; Yang Bo (Journal of Fluorescence, 2011)

Platelet adhesion and fusion to endothelial cell facilitate the metastasis of tumor cell in hypoxia-reoxygenation condition - Na Zhang; Wen-Jian Zhang; Han-Qing Cai; Hong-Lin Liu; Liang Peng; Cheng-Hui Li; Li-Ya Ye; Shi-Qing Xu; Zhi-Hua Yang; Jin-Ning Lou (Clinical & Experimental Metastasis, 2011)

Fractions and leaching characteristics of mercury in coal - Chun-Gang Yuan; Qing-Peng Li; Ya-Na Feng; Ai-Ling Chang (Environmental Monitoring and Assessment, 2010)

Isolation of high quality RNA and construction of a suppression subtractive hybridization library from ramie (Boehmeria nivea L. Gaud.) - Xu-xia Wang; Bo Wang; Li-jun Liu; Xiao-ping Cui; Jin-yu Yang; Hui Wang; Hui Jiang; Bei-bei Luo; Zhu Long; Wen-xiang Dou; Na Zhang; Ding-xiang Peng (Molecular Biology Reports, 2010)

Extended expression of B-class MADS-box genes in the paleoherb Asarum caudigerum - Yin-He Zhao; Michael Möller; Jun-Bo Yang; Ting-Song Liu; Jin-Feng Zhao; Li-Na Dong; Jin-Peng Zhang; Cheng-Yun Li; Guo-Ying Wang; De-Zhu Li (Planta, 2010)

Reciprocal regulation between M3 muscarinic acetylcholine receptor and protein kinase C-ε in ventricular myocytes during myocardial ischemia in rats - Peng-zhou Hang; Jing Zhao; Yu-ping Wang; Li-hua Sun; Yong Zhang; Li-li Yang; Na Zhao; Zhi-dan Sun; Yu-ying Mao; Zhi-min Du (Naunyn-Schmiedeberg's Archives of Pharmacology, 2009)

Genome-wide association scan for stature in Chinese: evidence for ethnic specific loci - Shu-Feng Lei; Tie-Lin Yang; Li-Jun Tan; Xiang-Ding Chen; Yan Guo; Yan-Fang Guo; Liang Zhang; Xiao-Gang Liu; Han Yan; Feng Pan; Zhi-Xin Zhang; Yu-Mei Peng; et al. (Human Genetics, 2009)

Purification of recombinant laccase from Trametes versicolor in Pichia methanolica and its use for the decolorization of anthraquinone dye - Mei Guo; Fuping Lu; Minyao Liu; Tuoping Li; Jun Pu; Na Wang; Peng Liang; Chenyun Zhang (Biotechnology Letters, 2008)

Rapid discrimination of H5 and H9 subtypes of avian influenza viruses and Newcastle disease virus by multiplex RT-PCR - Hao-tai Chen; Jie Zhang; De-hui Sun; Ji-le Zhang; Xue-peng Cai; Xiang-tao Liu; Yao-zhong Ding; Li-na Ma; Sheng-hai Yang; Lei Jin; Yongsheng Liu (Veterinary Research Communications, 2008)